Going back in time with TEMPO - Villalba Requena, Ana; Hippenmeyer, Simon (Neuron)
In this issue of Neuron, Espinosa-Medina et al.1 present the TEMPO (Temporal Encoding and Manipulation in a Predefined Order) system, which enables the marking and genetic manipulation of sequentially generated cell lineages in vertebrate species in vivo.

Single-molecule localization microscopy of presynaptic active zones in Drosophila melanogaster after rapid cryofixation - Mrestani, Achmed; Lichter, Katharina; Sirén, Anna Leena; Heckmann, Manfred; Paul, Mila M.; Pauli, Martin (International Journal of Molecular Sciences)
Single-molecule localization microscopy (SMLM) greatly advances structural studies of diverse biological tissues. For example, presynaptic active zone (AZ) nanotopology is resolved in increasing detail. Immunofluorescence imaging of AZ proteins usually relies on epitope preservation using aldehyde-based immunocompetent fixation. Cryofixation techniques, such as high-pressure freezing (HPF) and freeze substitution (FS), are widely used for ultrastructural studies of presynaptic architecture in electron microscopy (EM). HPF/FS demonstrated nearer-to-native preservation of AZ ultrastructure, e.g., by facilitating single filamentous structures. Here, we present a protocol combining the advantages of HPF/FS and direct stochastic optical reconstruction microscopy (dSTORM) to quantify nanotopology of the AZ scaffold protein Bruchpilot (Brp) at neuromuscular junctions (NMJs) of Drosophila melanogaster. Using this standardized model, we tested for preservation of Brp clusters in different FS protocols compared to classical aldehyde fixation. In HPF/FS samples, presynaptic boutons were structurally well preserved with ~22% smaller Brp clusters that allowed quantification of subcluster topology. In summary, we established a standardized near-to-native preparation and immunohistochemistry protocol for SMLM analyses of AZ protein clusters in a defined model synapse. Our protocol could be adapted to study protein arrangements at single-molecule resolution in other intact tissue preparations.

Wait-free approximate agreement on graphs - Alistarh, Dan-Adrian; Ellen, Faith; Rybicki, Joel (Theoretical Computer Science)
Approximate agreement is one of the few variants of consensus that can be solved in a wait-free manner in asynchronous systems where processes communicate by reading and writing to shared memory. In this work, we consider a natural generalisation of approximate agreement on arbitrary undirected connected graphs. Each process is given a node of the graph as input and, if non-faulty, must output a node such that – all the outputs are within distance 1 of one another, and – each output value lies on a shortest path between two input values. From prior work, it is known that there is no wait-free algorithm among processes for this problem on any cycle of length , by reduction from 2-set agreement (Castañeda et al., 2018). In this work, we investigate the solvability of this task on general graphs. We give a new, direct proof of the impossibility of approximate agreement on cycles of length , via a generalisation of Sperner's Lemma to convex polygons. We also extend the reduction from 2-set agreement to a larger class of graphs, showing that approximate agreement on these graphs is unsolvable. On the positive side, we present a wait-free algorithm for a different class of graphs, which properly contains the class of chordal graphs.

Elasto-inertial turbulence - Dubief, Yves; Terrapon, Vincent E.; Hof, Björn (Annual Review of Fluid Mechanics)
The dissolution of minute concentration of polymers in wall-bounded flows is well-known for its unparalleled ability to reduce turbulent friction drag. Another phenomenon, elasto-inertial turbulence (EIT), has been far less studied even though elastic instabilities have already been observed in dilute polymer solutions before the discovery of polymer drag reduction. EIT is a chaotic state driven by polymer dynamics that is observed across many orders of magnitude in Reynolds number. It involves energy transfer from small elastic scales to large flow scales. The investigation of the mechanisms of EIT offers the possibility to better understand other complex phenomena such as elastic turbulence and maximum drag reduction. In this review, we survey recent research efforts that are advancing the understanding of the dynamics of EIT. We highlight the fundamental differences between EIT and Newtonian/inertial turbulence from the perspective of experiments, numerical simulations, instabilities, and coherent structures. Finally, we discuss the possible links between EIT and elastic turbulence and polymer drag reduction, as well as the remaining challenges in unraveling the self-sustaining mechanism of EIT.

Transition to turbulence in pipe flow - Avila, Marc; Barkley, Dwight; Hof, Björn (Annual Review of Fluid Mechanics)
Since the seminal studies by Osborne Reynolds in the nineteenth century, pipe flow has served as a primary prototype for investigating the transition to turbulence in wall-bounded flows. Despite the apparent simplicity of this flow, various facets of this problem have occupied researchers for more than a century. Here we review insights from three distinct perspectives: (a) stability and susceptibility of laminar flow, (b) phase transition and spatiotemporal dynamics, and (c) dynamical systems analysis of the Navier—Stokes equations. We show how these perspectives have led to a profound understanding of the onset of turbulence in pipe flow. Outstanding open points, applications to flows of complex fluids, and similarities with other wall-bounded flows are discussed.

Steering self-organisation through confinement - Araújo, Nuno A.M.; Janssen, Liesbeth M.C.; Barois, Thomas; Boffetta, Guido; Cohen, Itai; Corbetta, Alessandro; Dauchot, Olivier; Dijkstra, Marjolein; Durham, William M.; Dussutour, Audrey; Garnier, Simon; Gelderblom, Hanneke; et al. (Soft Matter)
Self-organisation is the spontaneous emergence of spatio-temporal structures and patterns from the interaction of smaller individual units. Examples are found across many scales in very different systems and scientific disciplines, from physics, materials science and robotics to biology, geophysics and astronomy. Recent research has highlighted how self-organisation can be both mediated and controlled by confinement. Confinement is an action over a system that limits its units’ translational and rotational degrees of freedom, thus also influencing the system's phase space probability density; it can function as either a catalyst or inhibitor of self-organisation. Confinement can then become a means to actively steer the emergence or suppression of collective phenomena in space and time. Here, to provide a common framework and perspective for future research, we examine the role of confinement in the self-organisation of soft-matter systems and identify overarching scientific challenges that need to be addressed to harness its full scientific and technological potential in soft matter and related fields. By drawing analogies with other disciplines, this framework will accelerate a common deeper understanding of self-organisation and trigger the development of innovative strategies to steer it using confinement, with impact on, e.g., the design of smarter materials, tissue engineering for biomedicine and in guiding active matter.

Thermodynamics of diamond formation from hydrocarbon mixtures in planets - Cheng, Bingqing; Hamel, Sebastien; Bethkenhagen, Mandy (Nature Communications)
Hydrocarbon mixtures are extremely abundant in the Universe, and diamond formation from them can play a crucial role in shaping the interior structure and evolution of planets. With first-principles accuracy, we first estimate the melting line of diamond, and then reveal the nature of chemical bonding in hydrocarbons at extreme conditions. We finally establish the pressure-temperature phase boundary where it is thermodynamically possible for diamond to form from hydrocarbon mixtures with different atomic fractions of carbon. Notably, here we show a depletion zone at pressures above 200 GPa and temperatures below 3000 K-3500 K where diamond formation is thermodynamically favorable regardless of the carbon atomic fraction, due to a phase separation mechanism. The cooler condition of the interior of Neptune compared to Uranus means that the former is much more likely to contain the depletion zone. Our findings can help explain the dichotomy of the two ice giants manifested by the low luminosity of Uranus, and lead to a better understanding of (exo-)planetary formation and evolution.

Refining epigenetic prediction of chronological and biological age - Bernabeu, Elena; Mccartney, Daniel L.; Gadd, Danni A.; Hillary, Robert F.; Lu, Ake T.; Murphy, Lee; Wrobel, Nicola; Campbell, Archie; Harris, Sarah E.; Liewald, David; Hayward, Caroline; Sudlow, Cathie; et al. (Genome Medicine)
Background Epigenetic clocks can track both chronological age (cAge) and biological age (bAge). The latter is typically defined by physiological biomarkers and risk of adverse health outcomes, including all-cause mortality. As cohort sample sizes increase, estimates of cAge and bAge become more precise. Here, we aim to develop accurate epigenetic predictors of cAge and bAge, whilst improving our understanding of their epigenomic architecture. Methods First, we perform large-scale (N = 18,413) epigenome-wide association studies (EWAS) of chronological age and all-cause mortality. Next, to create a cAge predictor, we use methylation data from 24,674 participants from the Generation Scotland study, the Lothian Birth Cohorts (LBC) of 1921 and 1936, and 8 other cohorts with publicly available data. In addition, we train a predictor of time to all-cause mortality as a proxy for bAge using the Generation Scotland cohort (1214 observed deaths). For this purpose, we use epigenetic surrogates (EpiScores) for 109 plasma proteins and the 8 component parts of GrimAge, one of the current best epigenetic predictors of survival. We test this bAge predictor in four external cohorts (LBC1921, LBC1936, the Framingham Heart Study and the Women’s Health Initiative study). Results Through the inclusion of linear and non-linear age-CpG associations from the EWAS, feature pre-selection in advance of elastic net regression, and a leave-one-cohort-out (LOCO) cross-validation framework, we obtain cAge prediction with a median absolute error equal to 2.3 years. Our bAge predictor was found to slightly outperform GrimAge in terms of the strength of its association to survival (HRGrimAge = 1.47 [1.40, 1.54] with p = 1.08 × 10−52, and HRbAge = 1.52 [1.44, 1.59] with p = 2.20 × 10−60). Finally, we introduce MethylBrowsR, an online tool to visualise epigenome-wide CpG-age associations. Conclusions The integration of multiple large datasets, EpiScores, non-linear DNAm effects, and new approaches to feature selection has facilitated improvements to the blood-based epigenetic prediction of biological and chronological age.

Revisiting the adversarial robustness-accuracy tradeoff in robot learning - Lechner, Mathias; Amini, Alexander; Rus, Daniela; Henzinger, Thomas A (IEEE Robotics and Automation Letters)
Adversarial training (i.e., training on adversarially perturbed input data) is a well-studied method for making neural networks robust to potential adversarial attacks during inference. However, the improved robustness does not come for free but rather is accompanied by a decrease in overall model accuracy and performance. Recent work has shown that, in practical robot learning applications, the effects of adversarial training do not pose a fair trade-off but inflict a net loss when measured in holistic robot performance. This work revisits the robustness-accuracy trade-off in robot learning by systematically analyzing if recent advances in robust training methods and theory in conjunction with adversarial robot learning, are capable of making adversarial training suitable for real-world robot applications. We evaluate three different robot learning tasks ranging from autonomous driving in a high-fidelity environment amenable to sim-to-real deployment to mobile robot navigation and gesture recognition. Our results demonstrate that, while these techniques make incremental improvements on the trade-off on a relative scale, the negative impact on the nominal accuracy caused by adversarial training still outweighs the improved robustness by an order of magnitude. We conclude that although progress is happening, further advances in robust learning methods are necessary before they can benefit robot learning tasks in practice.

Highly adaptive nature of group 15 tris(quinolyl) ligands─studies with coinage metals - García-Romero, Álvaro; Waters, Jessica E.; Jethwa, Rajesh B; Bond, Andrew D.; Colebatch, Annie L.; García-Rodríguez, Raúl; Wright, Dominic S. (Inorganic Chemistry)
The substitution of heavier, more metallic atoms into classical organic ligand frameworks provides an important strategy for tuning ligand properties, such as ligand bite and donor character, and is the basis for the emerging area of main-group supramolecular chemistry. In this paper, we explore two new ligands [E(2-Me-8-qy)3] [E = Sb (1), Bi (2); qy = quinolyl], allowing a fundamental comparison of their coordination behavior with classical tris(2-pyridyl) ligands of the type [E′(2-py)3] (E = a range of bridgehead atoms and groups, py = pyridyl). A range of new coordination modes to Cu+, Ag+, and Au+ is seen for 1 and 2, in the absence of steric constraints at the bridgehead and with their more remote N-donor atoms. A particular feature is the adaptive nature of these new ligands, with the ability to adjust coordination mode in response to the hard–soft character of coordinated metal ions, influenced also by the character of the bridgehead atom (Sb or Bi). These features can be seen in a comparison between [Cu2{Sb(2-Me-8-qy)3}2](PF6)2 (1·CuPF6) and [Cu{Bi(2-Me-8-qy)3}](PF6) (2·CuPF6), the first containing a dimeric cation in which 1 adopts an unprecedented intramolecular N,N,Sb-coordination mode while in the second, 2 adopts an unusual N,N,(π-)C coordination mode. In contrast, the previously reported analogous ligands [E(6-Me-2-py)3] (E = Sb, Bi; 2-py = 2-pyridyl) show a tris-chelating mode in their complexes with CuPF6, which is typical for the extensive tris(2-pyridyl) family with a range of metals. The greater polarity of the Bi–C bond in 2 results in ligand transfer reactions with Au(I). Although this reactivity is not in itself unusual, the characterization of several products by single-crystal X-ray diffraction provides snapshots of the ligand transfer reaction involved, with one of the products (the bimetallic complex [(BiCl){ClAu2(2-Me-8-qy)3}] (8)) containing a Au2Bi core in which the shortest Au → Bi donor–acceptor bond to date is observed.

Spin-electric coupling in lead halide perovskites - Volosniev, Artem; Shiva Kumar, Abhishek; Lorenc, Dusan; Ashourishokri, Younes; Zhumekenov, Ayan A.; Bakr, Osman M.; Lemeshko, Mikhail; Alpichshev, Zhanybek (Physical Review Letters)
Lead halide perovskites enjoy a number of remarkable optoelectronic properties. To explain their origin, it is necessary to study how electromagnetic fields interact with these systems. We address this problem here by studying two classical quantities: Faraday rotation and the complex refractive index in a paradigmatic perovskite CH3NH3PbBr3 in a broad wavelength range. We find that the minimal coupling of electromagnetic fields to the k⋅p Hamiltonian is insufficient to describe the observed data even on the qualitative level. To amend this, we demonstrate that there exists a relevant atomic-level coupling between electromagnetic fields and the spin degree of freedom. This spin-electric coupling allows for quantitative description of a number of previous as well as present experimental data. In particular, we use it here to show that the Faraday effect in lead halide perovskites is dominated by the Zeeman splitting of the energy levels and has a substantial beyond-Becquerel contribution. Finally, we present general symmetry-based phenomenological arguments that in the low-energy limit our effective model includes all basis coupling terms to the electromagnetic field in the linear order.
Keywords: General Physics and Astronomy

Effective model for studying optical properties of lead halide perovskites - Volosniev, Artem; Shiva Kumar, Abhishek; Lorenc, Dusan; Ashourishokri, Younes; Zhumekenov, Ayan; Bakr, Osman M.; Lemeshko, Mikhail; Alpichshev, Zhanybek (Physical Review B)
We use general symmetry-based arguments to construct an effective model suitable for studying optical properties of lead halide perovskites. To build the model, we identify an atomic-level interaction between electromagnetic fields and the spin degree of freedom that should be added to a minimally coupled k⋅p Hamiltonian. As a first application, we study two basic optical characteristics of the material: the Verdet constant and the refractive index. Beyond these linear characteristics of the material, the model is suitable for calculating nonlinear effects such as the third-order optical susceptibility. Analysis of this quantity shows that the geometrical properties of the spin-electric term imply isotropic optical response of the system, and that optical anisotropy of lead halide perovskites is a manifestation of hopping of charge carriers. To illustrate this, we discuss third-harmonic generation.

Validation of a stereological method for estimating particle size and density from 2D projections with high accuracy - Rothman, Jason Seth; Borges Merjane, Carolina; Holderith, Noemi; Jonas, Peter M; Angus Silver, R. (PLoS ONE)
Stereological methods for estimating the 3D particle size and density from 2D projections are essential to many research fields. These methods are, however, prone to errors arising from undetected particle profiles due to sectioning and limited resolution, known as ‘lost caps’. A potential solution developed by Keiding, Jensen, and Ranek in 1972, which we refer to as the Keiding model, accounts for lost caps by quantifying the smallest detectable profile in terms of its limiting ‘cap angle’ (ϕ), a size-independent measure of a particle’s distance from the section surface. However, this simple solution has not been widely adopted nor tested. Rather, model-independent design-based stereological methods, which do not explicitly account for lost caps, have come to the fore. Here, we provide the first experimental validation of the Keiding model by comparing the size and density of particles estimated from 2D projections with direct measurement from 3D EM reconstructions of the same tissue. We applied the Keiding model to estimate the size and density of somata, nuclei and vesicles in the cerebellum of mice and rats, where high packing density can be problematic for design-based methods. Our analysis reveals a Gaussian distribution for ϕ rather than a single value. Nevertheless, curve fits of the Keiding model to the 2D diameter distribution accurately estimate the mean ϕ and 3D diameter distribution. While systematic testing using simulations revealed an upper limit to determining ϕ, our analysis shows that estimated ϕ can be used to determine the 3D particle density from the 2D density under a wide range of conditions, and this method is potentially more accurate than minimum-size-based lost-cap corrections and disector methods. Our results show the Keiding model provides an efficient means of accurately estimating the size and density of particles from 2D projections even under conditions of a high density.

The patterned assembly and stepwise Vps4-mediated disassembly of composite ESCRT-III polymers drives archaeal cell division - Hurtig, Fredrik; Burgers, Thomas C.Q.; Cezanne, Alice; Jiang, Xiuyun; Mol, Frank N.; Traparić, Jovan; Pulschen, Andre Arashiro; Nierhaus, Tim; Tarrason-Risa, Gabriel; Harker-Kirschneck, Lena; Löwe, Jan; Šarić, Anđela; et al. (Science Advances)
ESCRT-III family proteins form composite polymers that deform and cut membrane tubes in the context of a wide range of cell biological processes across the tree of life. In reconstituted systems, sequential changes in the composition of ESCRT-III polymers induced by the AAA–adenosine triphosphatase Vps4 have been shown to remodel membranes. However, it is not known how composite ESCRT-III polymers are organized and remodeled in space and time in a cellular context. Taking advantage of the relative simplicity of the ESCRT-III–dependent division system in Sulfolobus acidocaldarius, one of the closest experimentally tractable prokaryotic relatives of eukaryotes, we use super-resolution microscopy, electron microscopy, and computational modeling to show how CdvB/CdvB1/CdvB2 proteins form a precisely patterned composite ESCRT-III division ring, which undergoes stepwise Vps4-dependent disassembly and contracts to cut cells into two. These observations lead us to suggest sequential changes in a patterned composite polymer as a general mechanism of ESCRT-III–dependent membrane remodeling.

Using AlphaFold to predict the impact of single mutations on protein stability and function - Pak, Marina A.; Markhieva, Karina A.; Novikova, Mariia S.; Petrov, Dmitry S.; Vorobyev, Ilya S.; Maksimova, Ekaterina; Kondrashov, Fyodor; Ivankov, Dmitry N. (PLoS ONE)
AlphaFold changed the field of structural biology by achieving three-dimensional (3D) structure prediction from protein sequence at experimental quality. The astounding success even led to claims that the protein folding problem is “solved”. However, protein folding problem is more than just structure prediction from sequence. Presently, it is unknown if the AlphaFold-triggered revolution could help to solve other problems related to protein folding. Here we assay the ability of AlphaFold to predict the impact of single mutations on protein stability (ΔΔG) and function. To study the question we extracted the pLDDT and <pLDDT> metrics from AlphaFold predictions before and after single mutation in a protein and correlated the predicted change with the experimentally known ΔΔG values. Additionally, we correlated the same AlphaFold pLDDT metrics with the impact of a single mutation on structure using a large scale dataset of single mutations in GFP with the experimentally assayed levels of fluorescence. We found a very weak or no correlation between AlphaFold output metrics and change of protein stability or fluorescence. Our results imply that AlphaFold may not be immediately applied to other problems or applications in protein folding.

From the 'black box' to 'domino effect' mechanism: What have we learned from the structures of respiratory complex I - Sazanov, Leonid A (The Biochemical Journal)
My group and myself have studied respiratory complex I for almost 30 years, starting in 1994 when it was known as a L-shaped giant ‘black box' of bioenergetics. First breakthrough was the X-ray structure of the peripheral arm, followed by structures of the membrane arm and finally the entire complex from Thermus thermophilus. The developments in cryo-EM technology allowed us to solve the first complete structure of the twice larger, ∼1 MDa mammalian enzyme in 2016. However, the mechanism coupling, over large distances, the transfer of two electrons to pumping of four protons across the membrane remained an enigma. Recently we have solved high-resolution structures of mammalian and bacterial complex I under a range of redox conditions, including catalytic turnover. This allowed us to propose a robust and universal mechanism for complex I and related protein families. Redox reactions initially drive conformational changes around the quinone cavity and a long-distance transfer of substrate protons. These set up a stage for a series of electrostatically driven proton transfers along the membrane arm (‘domino effect'), eventually resulting in proton expulsion from the distal antiporter-like subunit. The mechanism radically differs from previous suggestions, however, it naturally explains all the unusual structural features of complex I. In this review I discuss the state of knowledge on complex I, including the current most controversial issues.

Coexistence times in the Moran process with environmental heterogeneity - Svoboda, Jakub; Tkadlec, Josef; Kaveh, Kamran; Chatterjee, Krishnendu (Proceedings of the Royal Society A: Mathematical, Physical and Engineering Sciences)
Populations evolve in spatially heterogeneous environments. While a certain trait might bring a fitness advantage in some patch of the environment, a different trait might be advantageous in another patch. Here, we study the Moran birth–death process with two types of individuals in a population stretched across two patches of size N, each patch favouring one of the two types. We show that the long-term fate of such populations crucially depends on the migration rate μ between the patches. To classify the possible fates, we use the distinction between polynomial (short) and exponential (long) timescales. We show that when μ is high then one of the two types fixates on the whole population after a number of steps that is only polynomial in N. By contrast, when μ is low then each type holds majority in the patch where it is favoured for a number of steps that is at least exponential in N. Moreover, we precisely identify the threshold migration rate μ⋆ that separates those two scenarios, thereby exactly delineating the situations that support long-term coexistence of the two types. We also discuss the case of various cycle graphs and we present computer simulations that perfectly match our analytical results.

Topological charges of periodically kicked molecules - Karle, Volker; Ghazaryan, Areg; Lemeshko, Mikhail (Physical Review Letters)
We show that the simplest of existing molecules—closed-shell diatomics not interacting with one another—host topological charges when driven by periodic far-off-resonant laser pulses. A periodically kicked molecular rotor can be mapped onto a “crystalline” lattice in angular momentum space. This allows us to define quasimomenta and the band structure in the Floquet representation, by analogy with the Bloch waves of solid-state physics. Applying laser pulses spaced by 1/3 of the molecular rotational period creates a lattice with three atoms per unit cell with staggered hopping. Within the synthetic dimension of the laser strength, we discover Dirac cones with topological charges. These Dirac cones, topologically protected by reflection and time-reversal symmetry, are reminiscent of (although not equivalent to) that seen in graphene. They—and the corresponding edge states—are broadly tunable by adjusting the laser strength and can be observed in present-day experiments by measuring molecular alignment and populations of rotational levels. This paves the way to study controllable topological physics in gas-phase experiments with small molecules as well as to classify dynamical molecular states by their topological invariants.

Multilayer graphenes as a platform for interaction-driven physics and topological superconductivity - Ghazaryan, Areg; Holder, Tobias; Berg, Erez; Serbyn, Maksym (Physical Review B)
Motivated by the recent discoveries of superconductivity in bilayer and trilayer graphene, we theoretically investigate superconductivity and other interaction-driven phases in multilayer graphene stacks. To this end, we study the density of states of multilayer graphene with up to four layers at the single-particle band structure level in the presence of a transverse electric field. Among the considered structures, tetralayer graphene with rhombohedral (ABCA) stacking reaches the highest density of states. We study the phases that can arise in ABCA graphene by tuning the carrier density and transverse electric field. For a broad region of the tuning parameters, the presence of strong Coulomb repulsion leads to a spontaneous spin and valley symmetry breaking via Stoner transitions. Using a model that incorporates the spontaneous spin and valley polarization, we explore the Kohn-Luttinger mechanism for superconductivity driven by repulsive Coulomb interactions. We find that the strongest superconducting instability is in the p-wave channel, and occurs in proximity to the onset of Stoner transitions. Interestingly, we find a range of densities and transverse electric fields where superconductivity develops out of a strongly corrugated, singly connected Fermi surface in each valley, leading to a topologically nontrivial chiral p+ip superconducting state with an even number of copropagating chiral Majorana edge modes. Our work establishes ABCA-stacked tetralayer graphene as a promising platform for observing strongly correlated physics and topological superconductivity.

Reconstructing Rayleigh–Bénard flows out of temperature-only measurements using Physics-Informed Neural Networks - Clark Di Leoni, Patricio; Agasthya, Lokahith N; Buzzicotti, Michele; Biferale, Luca (The European Physical Journal E)
We investigate the capabilities of Physics-Informed Neural Networks (PINNs) to reconstruct turbulent Rayleigh–Bénard flows using only temperature information. We perform a quantitative analysis of the quality of the reconstructions at various amounts of low-passed-filtered information and turbulent intensities. We compare our results with those obtained via nudging, a classical equation-informed data assimilation technique. At low Rayleigh numbers, PINNs are able to reconstruct with high precision, comparable to the one achieved with nudging. At high Rayleigh numbers, PINNs outperform nudging and are able to achieve satisfactory reconstruction of the velocity fields only when data for temperature is provided with high spatial and temporal density. When data becomes sparse, the PINNs performance worsens, not only in a point-to-point error sense but also, and contrary to nudging, in a statistical sense, as can be seen in the probability density functions and energy spectra.

A hydraulic feedback loop between mesendoderm cell migration and interstitial fluid relocalization promotes embryonic axis formation in zebrafish - Huljev, Karla; Shamipour, Shayan; Nunes Pinheiro, Diana C; Preusser, Friedrich; Steccari, Irene; Sommer, Christoph M; Naik, Suyash; Heisenberg, Carl-Philipp J (Developmental Cell)
Interstitial fluid (IF) accumulation between embryonic cells is thought to be important for embryo patterning and morphogenesis. Here, we identify a positive mechanical feedback loop between cell migration and IF relocalization and find that it promotes embryonic axis formation during zebrafish gastrulation. We show that anterior axial mesendoderm (prechordal plate [ppl]) cells, moving in between the yolk cell and deep cell tissue to extend the embryonic axis, compress the overlying deep cell layer, thereby causing IF to flow from the deep cell layer to the boundary between the yolk cell and the deep cell layer, directly ahead of the advancing ppl. This IF relocalization, in turn, facilitates ppl cell protrusion formation and migration by opening up the space into which the ppl moves and, thereby, the ability of the ppl to trigger IF relocalization by pushing against the overlying deep cell layer. Thus, embryonic axis formation relies on a hydraulic feedback loop between cell migration and IF relocalization.

Variational theory of angulons and their rotational spectroscopy - Zeng, Zhongda; Yakaboylu, Enderalp; Lemeshko, Mikhail; Shi, Tao; Schmidt, Richard (The Journal of Chemical Physics)
The angulon, a quasiparticle formed by a quantum rotor dressed by the excitations of a many-body bath, can be used to describe an impurity rotating in a fluid or solid environment. Here, we propose a coherent state ansatz in the co-rotating frame, which provides a comprehensive theoretical description of angulons. We reveal the quasiparticle properties, such as energies, quasiparticle weights, and spectral functions, and show that our ansatz yields a persistent decrease in the impurity’s rotational constant due to many-body dressing, which is consistent with experimental observations. From our study, a picture of the angulon emerges as an effective spin interacting with a magnetic field that is self-consistently generated by the molecule’s rotation. Moreover, we discuss rotational spectroscopy, which focuses on the response of rotating molecules to a laser perturbation in the linear response regime. Importantly, we take into account initial-state interactions that have been neglected in prior studies and reveal their impact on the excitation spectrum. To examine the angulon instability regime, we use a single-excitation ansatz and obtain results consistent with experiments, in which a broadening of spectral lines is observed while phonon wings remain highly suppressed due to initial-state interactions.

Superdiffusive energy transport in kinetically constrained models - Ljubotina, Marko; Desaules, Jean Yves; Serbyn, Maksym; Papić, Zlatko (Physical Review X)
Universal nonequilibrium properties of isolated quantum systems are typically probed by studying transport of conserved quantities, such as charge or spin, while transport of energy has received considerably less attention. Here, we study infinite-temperature energy transport in the kinetically constrained PXP model describing Rydberg atom quantum simulators. Our state-of-the-art numerical simulations, including exact diagonalization and time-evolving block decimation methods, reveal the existence of two distinct transport regimes. At moderate times, the energy-energy correlation function displays periodic oscillations due to families of eigenstates forming different su(2) representations hidden within the spectrum. These families of eigenstates generalize the quantum many-body scarred states found in previous works and leave an imprint on the infinite-temperature energy transport. At later times, we observe a long-lived superdiffusive transport regime that we attribute to the proximity of a nearby integrable point. While generic strong deformations of the PXP model indeed restore diffusive transport, adding a strong chemical potential intriguingly gives rise to a well-converged superdiffusive exponent z≈3/2. Our results suggest constrained models to be potential hosts of novel transport regimes and call for developing an analytic understanding of their energy transport.

A CrMnFeCoNi high entropy alloy boosting oxygen evolution/reduction reactions and zinc-air battery performance - He, Ren; Yang, Linlin; Zhang, Yu; Wang, Xiang; Lee, Seungho; Zhang, Ting; Li, Lingxiao; Liang, Zhifu; Chen, Jingwei; Li, Junshan; Ostovari Moghaddam, Ahmad; Llorca, Jordi; et al. (Energy Storage Materials)
The development of cost-effective, high-activity and stable bifunctional catalysts for the oxygen reduction and evolution reactions (ORR/OER) is essential for zinc–air batteries (ZABs) to reach the market. Such catalysts must contain multiple adsorption/reaction sites to cope with the high demands of reversible oxygen electrodes. Herein, we propose a high entropy alloy (HEA) based on relatively abundant elements as a bifunctional ORR/OER catalyst. More specifically, we detail the synthesis of a CrMnFeCoNi HEA through a low-temperature solution-based approach. Such HEA displays superior OER performance with an overpotential of 265 mV at a current density of 10 mA/cm2, and a 37.9 mV/dec Tafel slope, well above the properties of a standard commercial catalyst based on RuO2. This high performance is partially explained by the presence of twinned defects, the incidence of large lattice distortions, and the electronic synergy between the different components, being Cr key to decreasing the energy barrier of the OER rate-determining step. CrMnFeCoNi also displays superior ORR performance with a half-potential of 0.78 V and an onset potential of 0.88 V, comparable with commercial Pt/C. The potential gap (Egap) between the OER overpotential and the ORR half-potential of CrMnFeCoNi is just 0.734 V. Taking advantage of these outstanding properties, ZABs are assembled using the CrMnFeCoNi HEA as air cathode and a zinc foil as the anode. The assembled cells provide an open-circuit voltage of 1.489 V, i.e. 90% of its theoretical limit (1.66 V), a peak power density of 116.5 mW/cm2, and a specific capacity of 836 mAh/g that stays stable for more than 10 days of continuous cycling, i.e. 720 cycles @ 8 mA/cm2 and 16.6 days of continuous cycling, i.e. 1200 cycles @ 5 mA/cm2.

Rotation control, interlocking, and self‐positioning of active cogwheels - Martinet, Quentin; Aubret, Antoine; Palacci, Jérémie A (Advanced Intelligent Systems)
Gears and cogwheels are elemental components of machines. They restrain degrees of freedom and channel power into a specified motion. Building and powering small-scale cogwheels are key steps toward feasible micro and nanomachinery. Assembly, energy injection, and control are, however, a challenge at the microscale. In contrast with passive gears, whose function is to transmit torques from one to another, interlocking and untethered active gears have the potential to unveil dynamics and functions untapped by externally driven mechanisms. Here, it is shown the assembly and control of a family of self-spinning cogwheels with varying teeth numbers and study the interlocking of multiple cogwheels. The teeth are formed by colloidal microswimmers that power the structure. The cogwheels are autonomous and active, showing persistent rotation. Leveraging the angular momentum of optical vortices, we control the direction of rotation of the cogwheels. The pairs of interlocking and active cogwheels that roll over each other in a random walk and have curvature-dependent mobility are studied. This behavior is leveraged to self-position parts and program microbots, demonstrating the ability to pick up, direct, and release a load. The work constitutes a step toward autonomous machinery with external control as well as (re)programmable microbots and matter.

Curvature induces active velocity waves in rotating spherical tissues - Brandstätter, Tom; Brückner, David; Han, Yu Long; Alert, Ricard; Guo, Ming; Broedersz, Chase P. (Nature Communications)
The multicellular organization of diverse systems, including embryos, intestines, and tumors relies on coordinated cell migration in curved environments. In these settings, cells establish supracellular patterns of motion, including collective rotation and invasion. While such collective modes have been studied extensively in flat systems, the consequences of geometrical and topological constraints on collective migration in curved systems are largely unknown. Here, we discover a collective mode of cell migration in rotating spherical tissues manifesting as a propagating single-wavelength velocity wave. This wave is accompanied by an apparently incompressible supracellular flow pattern featuring topological defects as dictated by the spherical topology. Using a minimal active particle model, we reveal that this collective mode arises from the effect of curvature on the active flocking behavior of a cell layer confined to a spherical surface. Our results thus identify curvature-induced velocity waves as a mode of collective cell migration, impacting the dynamical organization of 3D curved tissues.

Overcoming photon blockade in a circuit-QED single-atom maser with engineered metastability and strong coupling - Sokolova, Alesya; Kalacheva, D. A.; Fedorov, G. P.; Astafiev, O. V. (Physical Review A)
Reaching a high cavity population with a coherent pump in the strong-coupling regime of a single-atom laser is impossible due to the photon blockade effect. In this Letter, we experimentally demonstrate that in a single-atom maser based on a transmon strongly coupled to two resonators, it is possible to pump over a dozen photons into the system. The first high-quality resonator plays the role of a usual lasing cavity, and the second one presents a controlled dissipation channel, bolstering population inversion, and modifies the energy-level structure to lift the blockade. As confirmation of the lasing action, we observe conventional laser features such as a narrowing of the emission linewidth and external signal amplification. Additionally, we report unique single-atom features: self-quenching and several lasing thresholds.

Quantitative assessment can stabilize indirect reciprocity under imperfect information - Schmid, Laura; Ekbatani, Farbod; Hilbe, Christian; Chatterjee, Krishnendu (Nature Communications)
The field of indirect reciprocity investigates how social norms can foster cooperation when individuals continuously monitor and assess each other’s social interactions. By adhering to certain social norms, cooperating individuals can improve their reputation and, in turn, receive benefits from others. Eight social norms, known as the “leading eight," have been shown to effectively promote the evolution of cooperation as long as information is public and reliable. These norms categorize group members as either ’good’ or ’bad’. In this study, we examine a scenario where individuals instead assign nuanced reputation scores to each other, and only cooperate with those whose reputation exceeds a certain threshold. We find both analytically and through simulations that such quantitative assessments are error-correcting, thus facilitating cooperation in situations where information is private and unreliable. Moreover, our results identify four specific norms that are robust to such conditions, and may be relevant for helping to sustain cooperation in natural populations.

Uncovering the organization of neural circuits with Generalized Phase Locking Analysis - Safavi, Shervin; Panagiotaropoulos, Theofanis I.; Kapoor, Vishal; Ramirez Villegas, Juan F; Logothetis, Nikos K.; Besserve, Michel (PLoS Computational Biology)
Despite the considerable progress of in vivo neural recording techniques, inferring the biophysical mechanisms underlying large scale coordination of brain activity from neural data remains challenging. One obstacle is the difficulty to link high dimensional functional connectivity measures to mechanistic models of network activity. We address this issue by investigating spike-field coupling (SFC) measurements, which quantify the synchronization between, on the one hand, the action potentials produced by neurons, and on the other hand mesoscopic “field” signals, reflecting subthreshold activities at possibly multiple recording sites. As the number of recording sites gets large, the amount of pairwise SFC measurements becomes overwhelmingly challenging to interpret. We develop Generalized Phase Locking Analysis (GPLA) as an interpretable dimensionality reduction of this multivariate SFC. GPLA describes the dominant coupling between field activity and neural ensembles across space and frequencies. We show that GPLA features are biophysically interpretable when used in conjunction with appropriate network models, such that we can identify the influence of underlying circuit properties on these features. We demonstrate the statistical benefits and interpretability of this approach in various computational models and Utah array recordings. The results suggest that GPLA, used jointly with biophysical modeling, can help uncover the contribution of recurrent microcircuits to the spatio-temporal dynamics observed in multi-channel experimental recordings.

Physics-inspired machine learning of localized intensive properties - Chen, Ke; Kunkel, Christian; Cheng, Bingqing; Reuter, Karsten; Margraf, Johannes T. (Chemical Science)
Machine learning (ML) has been widely applied to chemical property prediction, most prominently for the energies and forces in molecules and materials. The strong interest in predicting energies in particular has led to a ‘local energy’-based paradigm for modern atomistic ML models, which ensures size-extensivity and a linear scaling of computational cost with system size. However, many electronic properties (such as excitation energies or ionization energies) do not necessarily scale linearly with system size and may even be spatially localized. Using size-extensive models in these cases can lead to large errors. In this work, we explore different strategies for learning intensive and localized properties, using HOMO energies in organic molecules as a representative test case. In particular, we analyze the pooling functions that atomistic neural networks use to predict molecular properties, and suggest an orbital weighted average (OWA) approach that enables the accurate prediction of orbital energies and locations.

Salicylic acid inhibits rice endocytic protein trafficking mediated by OsPIN3t and clathrin to affect root growth - Jiang, Lihui; Yao, Baolin; Zhang, Xiaoyan; Wu, Lixia; Fu, Qijing; Zhao, Yiting; Cao, Yuxin; Zhu, Ruomeng; Lu, Xinqi; Huang, Wuying; Zhao, Jianping; Li, Kuixiu; et al. (Plant Journal)
Salicylic acid (SA) plays important roles in different aspects of plant development, including root growth, where auxin is also a major player by means of its asymmetric distribution. However, the mechanism underlying the effect of SA on the development of rice roots remains poorly understood. Here, we show that SA inhibits rice root growth by interfering with auxin transport associated with the OsPIN3t- and clathrin-mediated gene regulatory network (GRN). SA inhibits root growth as well as Brefeldin A-sensitive trafficking through a non-canonical SA signaling mechanism. Transcriptome analysis of rice seedlings treated with SA revealed that the OsPIN3t auxin transporter is at the center of a GRN involving the coat protein clathrin. The root growth and endocytic trafficking in both the pin3t and clathrin heavy chain mutants were SA insensitivity. SA inhibitory effect on the endocytosis of OsPIN3t was dependent on clathrin; however, the root growth and endocytic trafficking mediated by tyrphostin A23 (TyrA23) were independent of the pin3t mutant under SA treatment. These data reveal that SA affects rice root growth through the convergence of transcriptional and non-SA signaling mechanisms involving OsPIN3t-mediated auxin transport and clathrin-mediated trafficking as key components.

Boolean network sketches: A unifying framework for logical model inference - Beneš, Nikola; Brim, Luboš; Huvar, Ondřej; Pastva, Samuel; Šafránek, David (Bioinformatics)
Motivation: The problem of model inference is of fundamental importance to systems biology. Logical models (e.g. Boolean networks; BNs) represent a computationally attractive approach capable of handling large biological networks. The models are typically inferred from experimental data. However, even with a substantial amount of experimental data supported by some prior knowledge, existing inference methods often focus on a small sample of admissible candidate models only. Results: We propose Boolean network sketches as a new formal instrument for the inference of Boolean networks. A sketch integrates (typically partial) knowledge about the network’s topology and the update logic (obtained through, e.g. a biological knowledge base or a literature search), as well as further assumptions about the properties of the network’s transitions (e.g. the form of its attractor landscape), and additional restrictions on the model dynamics given by the measured experimental data. Our new BNs inference algorithm starts with an ‘initial’ sketch, which is extended by adding restrictions representing experimental data to a ‘data-informed’ sketch and subsequently computes all BNs consistent with the data-informed sketch. Our algorithm is based on a symbolic representation and coloured model-checking. Our approach is unique in its ability to cover a broad spectrum of knowledge and efficiently produce a compact representation of all inferred BNs. We evaluate the method on a non-trivial collection of real-world and simulated data.

Lamin B1 overexpression alters chromatin organization and gene expression - Kaneshiro, Jeanae M.; Capitanio, Juliana S.; Hetzer, Martin W (Nucleus)
Peripheral heterochromatin positioning depends on nuclear envelope associated proteins and repressive histone modifications. Here we show that overexpression (OE) of Lamin B1 (LmnB1) leads to the redistribution of peripheral heterochromatin into heterochromatic foci within the nucleoplasm. These changes represent a perturbation of heterochromatin binding at the nuclear periphery (NP) through a mechanism independent from altering other heterochromatin anchors or histone post-translational modifications. We further show that LmnB1 OE alters gene expression. These changes do not correlate with different levels of H3K9me3, but a significant number of the misregulated genes were likely mislocalized away from the NP upon LmnB1 OE. We also observed an enrichment of developmental processes amongst the upregulated genes. ~74% of these genes were normally repressed in our cell type, suggesting that LmnB1 OE promotes gene de-repression. This demonstrates a broader consequence of LmnB1 OE on cell fate, and highlights the importance of maintaining proper levels of LmnB1.

Numerical quantum clock simulations for measuring tunneling times - Suzuki, Fumika; Unruh, William G. (Physical Review A)
We numerically study two methods of measuring tunneling times using a quantum clock. In the conventional method using the Larmor clock, we show that the Larmor tunneling time can be shorter for higher tunneling barriers. In the second method, we study the probability of a spin-flip of a particle when it is transmitted through a potential barrier including a spatially rotating field interacting with its spin. According to the adiabatic theorem, the probability depends on the velocity of the particle inside the barrier. It is numerically observed that the probability increases for higher barriers, which is consistent with the result obtained by the Larmor clock. By comparing outcomes for different initial spin states, we suggest that one of the main causes of the apparent decrease in the tunneling time can be the filtering effect occurring at the end of the barrier.

Symmetry-broken Josephson junctions and superconducting diodes in magic-angle twisted bilayer graphene - Díez-Mérida, J.; Díez-Carlón, A.; Yang, S. Y.; Xie, Y. M.; Gao, X. J.; Senior, Jorden L; Watanabe, K.; Taniguchi, T.; Lu, X.; Higginbotham, Andrew P; Law, K. T.; Efetov, Dmitri K. (Nature Communications)
The coexistence of gate-tunable superconducting, magnetic and topological orders in magic-angle twisted bilayer graphene provides opportunities for the creation of hybrid Josephson junctions. Here we report the fabrication of gate-defined symmetry-broken Josephson junctions in magic-angle twisted bilayer graphene, where the weak link is gate-tuned close to the correlated insulator state with a moiré filling factor of υ = −2. We observe a phase-shifted and asymmetric Fraunhofer pattern with a pronounced magnetic hysteresis. Our theoretical calculations of the junction weak link—with valley polarization and orbital magnetization—explain most of these unconventional features. The effects persist up to the critical temperature of 3.5 K, with magnetic hysteresis observed below 800 mK. We show how the combination of magnetization and its current-induced magnetization switching allows us to realise a programmable zero-field superconducting diode. Our results represent a major advance towards the creation of future superconducting quantum electronic devices.

Global renormalised solutions and equilibration of reaction-diffusion systems with non-linear diffusion - Fellner, Klemens; Fischer, Julian L; Kniely, Michael; Tang, Bao Quoc (Journal of Nonlinear Science)
The global existence of renormalised solutions and convergence to equilibrium for reaction-diffusion systems with non-linear diffusion are investigated. The system is assumed to have quasi-positive non-linearities and to satisfy an entropy inequality. The difficulties in establishing global renormalised solutions caused by possibly degenerate diffusion are overcome by introducing a new class of weighted truncation functions. By means of the obtained global renormalised solutions, we study the large-time behaviour of complex balanced systems arising from chemical reaction network theory with non-linear diffusion. When the reaction network does not admit boundary equilibria, the complex balanced equilibrium is shown, by using the entropy method, to exponentially attract all renormalised solutions in the same compatibility class. This convergence extends even to a range of non-linear diffusion, where global existence is an open problem, yet we are able to show that solutions to approximate systems converge exponentially to equilibrium uniformly in the regularisation parameter.

Weak-strong uniqueness for the mean curvature flow of double bubbles - Hensel, Sebastian; Laux, Tim (Interfaces and Free Boundaries)
We derive a weak-strong uniqueness principle for BV solutions to multiphase mean curvature flow of triple line clusters in three dimensions. Our proof is based on the explicit construction of a gradient flow calibration in the sense of the recent work of Fischer et al. (2020) for any such cluster. This extends the two-dimensional construction to the three-dimensional case of surfaces meeting along triple junctions.

Computing chemical potentials of adsorbed or confined fluids - Schmid, Rochus; Cheng, Bingqing (The Journal of Chemical Physics)
The chemical potential of adsorbed or confined fluids provides insight into their unique thermodynamic properties and determines adsorption isotherms. However, it is often difficult to compute this quantity from atomistic simulations using existing statistical mechanical methods. We introduce a computational framework that utilizes static structure factors, thermodynamic integration, and free energy perturbation for calculating the absolute chemical potential of fluids. For demonstration, we apply the method to compute the adsorption isotherms of carbon dioxide in a metal-organic framework and water in carbon nanotubes.

Directionality-aware design of embroidery patterns - Liu, Zhenyuan; Piovarci, Michael; Hafner, Christian; Charrondiere, Raphael; Bickel, Bernd (Computer Graphics Forum)
Embroidery is a long-standing and high-quality approach to making logos and images on textiles. Nowadays, it can also be performed via automated machines that weave threads with high spatial accuracy. A characteristic feature of the appearance of the threads is a high degree of anisotropy. The anisotropic behavior is caused by depositing thin but long strings of thread. As a result, the stitched patterns convey both color and direction. Artists leverage this anisotropic behavior to enhance pure color images with textures, illusions of motion, or depth cues. However, designing colorful embroidery patterns with prescribed directionality is a challenging task, one usually requiring an expert designer. In this work, we propose an interactive algorithm that generates machine-fabricable embroidery patterns from multi-chromatic images equipped with user-specified directionality fields.We cast the problem of finding a stitching pattern into vector theory. To find a suitable stitching pattern, we extract sources and sinks from the divergence field of the vector field extracted from the input and use them to trace streamlines. We further optimize the streamlines to guarantee a smooth and connected stitching pattern. The generated patterns approximate the color distribution constrained by the directionality field. To allow for further artistic control, the trade-off between color match and directionality match can be interactively explored via an intuitive slider. We showcase our approach by fabricating several embroidery paths.
Keywords: embroidery; design; directionality; density; image

Disulfide-bond-induced structural frustration and dynamic disorder in a peroxiredoxin from MAS NMR - Troussicot, Laura; Vallet, Alicia; Molin, Mikael; Burmann, Björn M.; Schanda, Paul (Journal of the American Chemical Society)
Disulfide bond formation is fundamentally important for protein structure and constitutes a key mechanism by which cells regulate the intracellular oxidation state. Peroxiredoxins (PRDXs) eliminate reactive oxygen species such as hydrogen peroxide through a catalytic cycle of Cys oxidation and reduction. Additionally, upon Cys oxidation PRDXs undergo extensive conformational rearrangements that may underlie their presently structurally poorly defined functions as molecular chaperones. Rearrangements include high molecular-weight oligomerization, the dynamics of which are, however, poorly understood, as is the impact of disulfide bond formation on these properties. Here we show that formation of disulfide bonds along the catalytic cycle induces extensive μs time scale dynamics, as monitored by magic-angle spinning NMR of the 216 kDa-large Tsa1 decameric assembly and solution-NMR of a designed dimeric mutant. We ascribe the conformational dynamics to structural frustration, resulting from conflicts between the disulfide-constrained reduction of mobility and the desire to fulfill other favorable contacts.

A note on long cycles in sparse random graphs - Anastos, Michael (Electronic Journal of Combinatorics)
Let Lc,n denote the size of the longest cycle in G(n, c/n),c >1 constant. We show that there exists a continuous function f(c) such that Lc,n/n→f(c) a.s. for c>20, thus extending a result of Frieze and the author to smaller values of c. Thereafter, for c>20, we determine the limit of the probability that G(n, c/n)contains cycles of every length between the length of its shortest and its longest cycles as n→∞.

Research data of the publication "Disulfide-bond-induced structural frustration and dynamic disorder in a peroxiredoxin from MAS NMR" - Schanda, Paul
Disulfide bond formation is fundamentally important for protein structure, and constitutes a key mechanism by which cells regulate the intracellular oxidation state. Peroxiredoxins (PRDXs) eliminate reactive oxygen species such as hydrogen peroxide through a catalytic cycle of Cys oxidation and reduction. Additionally, upon Cys oxidation PRDXs undergo extensive conformational rearrangements that may underlie their presently structurally poorly defined functions as molecular chaperones. Rearrangements include high molecular-weight oligomerization, the dynamics of which are, however, poorly understood, as is the impact of disulfide bond formation on these properties. Here we show that formation of disulfide bonds along the catalytic cycle induces extensive microsecond time scale dynamics, as monitored by magic-angle spinning NMR of the 216 kDa-large Tsa1 decameric assembly and solution-NMR of a designed dimeric mutant. We ascribe the conformational dynamics to structural frustration, resulting from conflicts between the disulfide-constrained reduction of mobility and the desire to fulfil other favorable contacts. This data repository contains NMR data presented in the associated manuscript

Ab initio calculation of the reflectivity of molecular fluids under shock compression - French, Martin; Bethkenhagen, Mandy; Ravasio, Alessandra; Hernandez, Jean Alexis (Physical Review B)
We calculate reflectivities of dynamically compressed water, water-ethanol mixtures, and ammonia at infrared and optical wavelengths with density functional theory and molecular dynamics simulations. The influence of the exchange-correlation functional on the results is examined in detail. Our findings indicate that the consistent use of the HSE hybrid functional reproduces experimental results much better than the commonly used PBE functional. The HSE functional offers not only a more accurate description of the electronic band gap but also shifts the onset of molecular dissociation in the molecular dynamics simulations to significantly higher pressures. We also highlight the importance of using accurate reference standards in reflectivity experiments and reanalyze infrared and optical reflectivity data from recent experiments. Thus, our combined theoretical and experimental work explains and resolves lingering discrepancies between calculations and measurements for the investigated molecular substances under shock compression.

Bottom-up synthesis of SnTe-based thermoelectric composites - Nan, Bingfei; Song, Xuan; Chang, Cheng; Xiao, Ke; Zhang, Yu; Yang, Linlin; Horta, Sharona; Li, Junshan; Lim, Khak Ho; Ibáñez, Maria; Cabot, Andreu (ACS Applied Materials and Interfaces)
There is a need for the development of lead-free thermoelectric materials for medium-/high-temperature applications. Here, we report a thiol-free tin telluride (SnTe) precursor that can be thermally decomposed to produce SnTe crystals with sizes ranging from tens to several hundreds of nanometers. We further engineer SnTe–Cu2SnTe3 nanocomposites with a homogeneous phase distribution by decomposing the liquid SnTe precursor containing a dispersion of Cu1.5Te colloidal nanoparticles. The presence of Cu within the SnTe and the segregated semimetallic Cu2SnTe3 phase effectively improves the electrical conductivity of SnTe while simultaneously reducing the lattice thermal conductivity without compromising the Seebeck coefficient. Overall, power factors up to 3.63 mW m–1 K–2 and thermoelectric figures of merit up to 1.04 are obtained at 823 K, which represent a 167% enhancement compared with pristine SnTe.

Wrapping pathways of anisotropic dumbbell particles by Giant Unilamellar Vesicles - Azadbakht, Ali; Meadowcroft, Billie; Varkevisser, Thijs; Šarić, Anđela; Kraft, Daniela J. (Nano Letters)
Endocytosis is a key cellular process involved in the uptake of nutrients, pathogens, or the therapy of diseases. Most studies have focused on spherical objects, whereas biologically relevant shapes can be highly anisotropic. In this letter, we use an experimental model system based on Giant Unilamellar Vesicles (GUVs) and dumbbell-shaped colloidal particles to mimic and investigate the first stage of the passive endocytic process: engulfment of an anisotropic object by the membrane. Our model has specific ligand–receptor interactions realized by mobile receptors on the vesicles and immobile ligands on the particles. Through a series of experiments, theory, and molecular dynamics simulations, we quantify the wrapping process of anisotropic dumbbells by GUVs and identify distinct stages of the wrapping pathway. We find that the strong curvature variation in the neck of the dumbbell as well as membrane tension are crucial in determining both the speed of wrapping and the final states.

Engineering of thermoelectric composites based on silver selenide in aqueous solution and ambient temperature - Nan, Bingfei; Li, Mengyao; Zhang, Yu; Xiao, Ke; Lim, Khak Ho; Chang, Cheng; Han, Xu; Zuo, Yong; Li, Junshan; Arbiol, Jordi; Llorca, Jordi; Ibáñez, Maria; et al. (ACS Applied Electronic Materials)
The direct, solid state, and reversible conversion between heat and electricity using thermoelectric devices finds numerous potential uses, especially around room temperature. However, the relatively high material processing cost limits their real applications. Silver selenide (Ag2Se) is one of the very few n-type thermoelectric (TE) materials for room-temperature applications. Herein, we report a room temperature, fast, and aqueous-phase synthesis approach to produce Ag2Se, which can be extended to other metal chalcogenides. These materials reach TE figures of merit (zT) of up to 0.76 at 380 K. To improve these values, bismuth sulfide (Bi2S3) particles also prepared in an aqueous solution are incorporated into the Ag2Se matrix. In this way, a series of Ag2Se/Bi2S3 composites with Bi2S3 wt % of 0.5, 1.0, and 1.5 are prepared by solution blending and hot-press sintering. The presence of Bi2S3 significantly improves the Seebeck coefficient and power factor while at the same time decreasing the thermal conductivity with no apparent drop in electrical conductivity. Thus, a maximum zT value of 0.96 is achieved in the composites with 1.0 wt % Bi2S3 at 370 K. Furthermore, a high average zT value (zTave) of 0.93 in the 300–390 K range is demonstrated.

Free rational curves on low degree hypersurfaces and the circle method - Browning, Timothy D; Sawin, Will (Algebra and Number Theory)
We use a function field version of the Hardy–Littlewood circle method to study the locus of free rational curves on an arbitrary smooth projective hypersurface of sufficiently low degree. On the one hand this allows us to bound the dimension of the singular locus of the moduli space of rational curves on such hypersurfaces and, on the other hand, it sheds light on Peyre’s reformulation of the Batyrev–Manin conjecture in terms of slopes with respect to the tangent bundle.

Tunable directional photon scattering from a pair of superconducting qubits - Redchenko, Elena; Poshakinskiy, Alexander V.; Sett, Riya; Zemlicka, Martin; Poddubny, Alexander N.; Fink, Johannes M (Nature Communications)
The ability to control the direction of scattered light is crucial to provide flexibility and scalability for a wide range of on-chip applications, such as integrated photonics, quantum information processing, and nonlinear optics. Tunable directionality can be achieved by applying external magnetic fields that modify optical selection rules, by using nonlinear effects, or interactions with vibrations. However, these approaches are less suitable to control microwave photon propagation inside integrated superconducting quantum devices. Here, we demonstrate on-demand tunable directional scattering based on two periodically modulated transmon qubits coupled to a transmission line at a fixed distance. By changing the relative phase between the modulation tones, we realize unidirectional forward or backward photon scattering. Such an in-situ switchable mirror represents a versatile tool for intra- and inter-chip microwave photonic processors. In the future, a lattice of qubits can be used to realize topological circuits that exhibit strong nonreciprocity or chirality.

Entangling microwaves with light - Sahu, Rishabh; Qiu, Liu; Hease, William J; Arnold, Georg M; Minoguchi, Y.; Rabl, P.; Fink, Johannes M (Science)
Quantum entanglement is a key resource in currently developed quantum technologies. Sharing this fragile property between superconducting microwave circuits and optical or atomic systems would enable new functionalities, but this has been hindered by an energy scale mismatch of >104 and the resulting mutually imposed loss and noise. In this work, we created and verified entanglement between microwave and optical fields in a millikelvin environment. Using an optically pulsed superconducting electro-optical device, we show entanglement between propagating microwave and optical fields in the continuous variable domain. This achievement not only paves the way for entanglement between superconducting circuits and telecom wavelength light, but also has wide-ranging implications for hybrid quantum networks in the context of modularization, scaling, sensing, and cross-platform verification.
Keywords: Multidisciplinary

Bias in the representative volume element method: Periodize the ensemble instead of its realizations - Clozeau, Nicolas; Josien, Marc; Otto, Felix; Xu, Qiang (Foundations of Computational Mathematics)
We study the representative volume element (RVE) method, which is a method to approximately infer the effective behavior ahom of a stationary random medium. The latter is described by a coefficient field a(x) generated from a given ensemble ⟨⋅⟩ and the corresponding linear elliptic operator −∇⋅a∇. In line with the theory of homogenization, the method proceeds by computing d=3 correctors (d denoting the space dimension). To be numerically tractable, this computation has to be done on a finite domain: the so-called representative volume element, i.e., a large box with, say, periodic boundary conditions. The main message of this article is: Periodize the ensemble instead of its realizations. By this, we mean that it is better to sample from a suitably periodized ensemble than to periodically extend the restriction of a realization a(x) from the whole-space ensemble ⟨⋅⟩. We make this point by investigating the bias (or systematic error), i.e., the difference between ahom and the expected value of the RVE method, in terms of its scaling w.r.t. the lateral size L of the box. In case of periodizing a(x), we heuristically argue that this error is generically O(L−1). In case of a suitable periodization of ⟨⋅⟩ , we rigorously show that it is O(L−d). In fact, we give a characterization of the leading-order error term for both strategies and argue that even in the isotropic case it is generically non-degenerate. We carry out the rigorous analysis in the convenient setting of ensembles ⟨⋅⟩ of Gaussian type, which allow for a straightforward periodization, passing via the (integrable) covariance function. This setting has also the advantage of making the Price theorem and the Malliavin calculus available for optimal stochastic estimates of correctors. We actually need control of second-order correctors to capture the leading-order error term. This is due to inversion symmetry when applying the two-scale expansion to the Green function. As a bonus, we present a stream-lined strategy to estimate the error in a higher-order two-scale expansion of the Green function.

Tunable directional photon scattering from a pair of superconducting qubits - Redchenko, Elena; Poshakinskiy, Alexander; Sett, Riya; Zemlicka, Martin; Poddubny, Alexander; Fink, Johannes M
This dataset comprises all data shown in the figures of the submitted article "Tunable directional photon scattering from a pair of superconducting qubits" at arXiv:2205.03293. Additional raw data are available from the corresponding author on reasonable request.

Entangling microwaves with light - Sahu, Rishabh
Data for submitted article "Entangling microwaves with light" at arXiv:2301.03315v1

Multi-copper oxidases SKU5 and SKS1 coordinate cell wall formation using apoplastic redox-based reactions in roots - Chen, C; Zhang, Y; Cai, J; Qiu, Y; Li, L; Gao, C; Gao, Y; Ke, M; Wu, S; Wei, C; Chen, J; Xu, T; et al. (Plant Physiology)
The primary cell wall is a fundamental plant constituent that is flexible but sufficiently rigid to support the plant cell shape. Although many studies have demonstrated that reactive oxygen species (ROS) serve as important signaling messengers to modify the cell wall structure and affect cellular growth, the regulatory mechanism underlying the spatial-temporal regulation of ROS activity for cell wall maintenance remains largely unclear. Here, we demonstrate the role of the Arabidopsis (Arabidopsis thaliana) multicopper oxidase-like protein skewed 5 (SKU5) and its homolog SKU5-similar 1 (SKS1) in root cell wall formation through modulating ROS homeostasis. Loss of SKU5 and SKS1 function resulted in aberrant division planes, protruding cell walls, ectopic deposition of iron, and reduced nicotinamide adeninedinucleotide phosphate (NADPH) oxidase-dependent ROS overproduction in the root epidermis–cortex and cortex–endodermis junctions. A decrease in ROS level or inhibition of NADPH oxidase activity rescued the cell wall defects of sku5 sks1 double mutants. SKU5 and SKS1 proteins were activated by iron treatment, and iron over-accumulated in the walls between the root epidermis and cortex cell layers of sku5 sks1. The glycosylphosphatidylinositol-anchored motif was crucial for membrane association and functionality of SKU5 and SKS1. Overall, our results identified SKU5 and SKS1 as regulators of ROS at the cell surface for regulation of cell wall structure and root cell growth.

Monitoring lineages of growing and dividing bacteria reveals an inducible memory of mar operon expression - Guet, Calin C; Bruneaux, L; Oikonomou, P; Aldana, M; Cluzel, P (Frontiers in Microbiology)
In Gram negative bacteria, the multiple antibiotic resistance or mar operon, is known to control the expression of multi-drug efflux genes that protect bacteria from a wide range of drugs. As many different chemical compounds can induce this operon, identifying the parameters that govern the dynamics of its induction is crucial to better characterize the processes of tolerance and resistance. Most experiments have assumed that the properties of the mar transcriptional network can be inferred from population measurements. However, measurements from an asynchronous population of cells can mask underlying phenotypic variations of single cells. We monitored the activity of the mar promoter in single Escherichia coli cells in linear micro-colonies and established that the response to a steady level of inducer was most heterogeneous within individual colonies for an intermediate value of inducer. Specifically, sub-lineages defined by contiguous daughter-cells exhibited similar promoter activity, whereas activity was greatly variable between different sub-lineages. Specific sub-trees of uniform promoter activity persisted over several generations. Statistical analyses of the lineages suggest that the presence of these sub-trees is the signature of an inducible memory of the promoter state that is transmitted from mother to daughter cells. This single-cell study reveals that the degree of epigenetic inheritance changes as a function of inducer concentration, suggesting that phenotypic inheritance may be an inducible phenotype.

Amyloid formation as a protein phase transition - Michaels, Thomas C.T.; Qian, Daoyuan; Šarić, Anđela; Vendruscolo, Michele; Linse, Sara; Knowles, Tuomas P.J. (Nature Reviews Physics)
The formation of amyloid fibrils is a general class of protein self-assembly behaviour, which is associated with both functional biology and the development of a number of disorders, such as Alzheimer and Parkinson diseases. In this Review, we discuss how general physical concepts from the study of phase transitions can be used to illuminate the fundamental mechanisms of amyloid self-assembly. We summarize progress in the efforts to describe the essential biophysical features of amyloid self-assembly as a nucleation-and-growth process and discuss how master equation approaches can reveal the key molecular pathways underlying this process, including the role of secondary nucleation. Additionally, we outline how non-classical aspects of aggregate formation involving oligomers or biomolecular condensates have emerged, inspiring developments in understanding, modelling and modulating complex protein assembly pathways. Finally, we consider how these concepts can be applied to kinetics-based drug discovery and therapeutic design to develop treatments for protein aggregation diseases.

Yolk granule fusion and microtubule aster formation regulate cortical granule translocation and exocytosis in zebrafish oocytes - Shamipour, Shayan; Hofmann, Laura; Steccari, Irene; Kardos, Roland; Heisenberg, Carl-Philipp J (PLoS Biology)
Dynamic reorganization of the cytoplasm is key to many core cellular processes, such as cell division, cell migration, and cell polarization. Cytoskeletal rearrangements are thought to constitute the main drivers of cytoplasmic flows and reorganization. In contrast, remarkably little is known about how dynamic changes in size and shape of cell organelles affect cytoplasmic organization. Here, we show that within the maturing zebrafish oocyte, the surface localization of exocytosis-competent cortical granules (Cgs) upon germinal vesicle breakdown (GVBD) is achieved by the combined activities of yolk granule (Yg) fusion and microtubule aster formation and translocation. We find that Cgs are moved towards the oocyte surface through radially outward cytoplasmic flows induced by Ygs fusing and compacting towards the oocyte center in response to GVBD. We further show that vesicles decorated with the small Rab GTPase Rab11, a master regulator of vesicular trafficking and exocytosis, accumulate together with Cgs at the oocyte surface. This accumulation is achieved by Rab11-positive vesicles being transported by acentrosomal microtubule asters, the formation of which is induced by the release of CyclinB/Cdk1 upon GVBD, and which display a net movement towards the oocyte surface by preferentially binding to the oocyte actin cortex. We finally demonstrate that the decoration of Cgs by Rab11 at the oocyte surface is needed for Cg exocytosis and subsequent chorion elevation, a process central in egg activation. Collectively, these findings unravel a yet unrecognized role of organelle fusion, functioning together with cytoskeletal rearrangements, in orchestrating cytoplasmic organization during oocyte maturation.

Asymmetries in triboelectric charging: Generalizing mosaic models to different-material samples and sliding contacts - Grosjean, Galien M; Waitukaitis, Scott R (Physical Review Materials)
Nominally identical materials exchange net electric charge during contact through a mechanism that is still debated. ‘Mosaic models’, in which surfaces are presumed to consist of a random patchwork of microscopic donor/acceptor sites, offer an appealing explanation for this phenomenon. However, recent experiments have shown that global differences persist even between same-material samples, which the standard mosaic framework does not account for. Here, we expand the mosaic framework by incorporating global differences in the densities of donor/acceptor sites. We develop an analytical model, backed by numerical simulations, that smoothly connects the global and deterministic charge transfer of different materials to the local and stochastic mosaic picture normally associated with identical materials. Going further, we extend our model to explain the effect of contact asymmetries during sliding, providing a plausible explanation for reversal of charging sign that has been observed experimentally.
Keywords: Physics and Astronomy (miscellaneous); General Materials Science

Environmental dynamics shape perceptual decision bias - Charlton, Julie A.; Mlynarski, Wiktor F; Bai, Yoon H.; Hermundstad, Ann M.; Goris, Robbe L.T. (PLoS Computational Biology)
To interpret the sensory environment, the brain combines ambiguous sensory measurements with knowledge that reflects context-specific prior experience. But environmental contexts can change abruptly and unpredictably, resulting in uncertainty about the current context. Here we address two questions: how should context-specific prior knowledge optimally guide the interpretation of sensory stimuli in changing environments, and do human decision-making strategies resemble this optimum? We probe these questions with a task in which subjects report the orientation of ambiguous visual stimuli that were drawn from three dynamically switching distributions, representing different environmental contexts. We derive predictions for an ideal Bayesian observer that leverages knowledge about the statistical structure of the task to maximize decision accuracy, including knowledge about the dynamics of the environment. We show that its decisions are biased by the dynamically changing task context. The magnitude of this decision bias depends on the observer’s continually evolving belief about the current context. The model therefore not only predicts that decision bias will grow as the context is indicated more reliably, but also as the stability of the environment increases, and as the number of trials since the last context switch grows. Analysis of human choice data validates all three predictions, suggesting that the brain leverages knowledge of the statistical structure of environmental change when interpreting ambiguous sensory signals.

Design and immunogenicity of SARS-CoV-2 DNA vaccine encoding RBD-PVXCP fusion protein - Dormeshkin, Dmitri; Katsin, Mikalai; Stegantseva, Maria; Golenchenko, Sergey; Shapira, Michail; Dubovik, Simon; Lutskovich, Dzmitry; Kavaleuski, Anton; Meleshko, Alexander (Vaccines)
The potential of immune-evasive mutation accumulation in the SARS-CoV-2 virus has led to its rapid spread, causing over 600 million confirmed cases and more than 6.5 million confirmed deaths. The huge demand for the rapid development and deployment of low-cost and effective vaccines against emerging variants has renewed interest in DNA vaccine technology. Here, we report the rapid generation and immunological evaluation of novel DNA vaccine candidates against the Wuhan-Hu-1 and Omicron variants based on the RBD protein fused with the Potato virus X coat protein (PVXCP). The delivery of DNA vaccines using electroporation in a two-dose regimen induced high-antibody titers and profound cellular responses in mice. The antibody titers induced against the Omicron variant of the vaccine were sufficient for effective protection against both Omicron and Wuhan-Hu-1 virus infections. The PVXCP protein in the vaccine construct shifted the immune response to the favorable Th1-like type and provided the oligomerization of RBD-PVXCP protein. Naked DNA delivery by needle-free injection allowed us to achieve antibody titers comparable with mRNA-LNP delivery in rabbits. These data identify the RBD-PVXCP DNA vaccine platform as a promising solution for robust and effective SARS-CoV-2 protection, supporting further translational study.

Surface chemistry and band engineering in AgSbSe₂: Toward high thermoelectric performance - Liu, Yu; Li, Mingquan; Wan, Shanhong; Lim, Khak Ho; Zhang, Yu; Li, Mengyao; Li, Junshan; Ibáñez, Maria; Hong, Min; Cabot, Andreu (ACS Nano)
AgSbSe2 is a promising thermoelectric (TE) p-type material for applications in the middle-temperature range. AgSbSe2 is characterized by relatively low thermal conductivities and high Seebeck coefficients, but its main limitation is moderate electrical conductivity. Herein, we detail an efficient and scalable hot-injection synthesis route to produce AgSbSe2 nanocrystals (NCs). To increase the carrier concentration and improve the electrical conductivity, these NCs are doped with Sn2+ on Sb3+ sites. Upon processing, the Sn2+ chemical state is conserved using a reducing NaBH4 solution to displace the organic ligand and anneal the material under a forming gas flow. The TE properties of the dense materials obtained from the consolidation of the NCs using a hot pressing are then characterized. The presence of Sn2+ ions replacing Sb3+ significantly increases the charge carrier concentration and, consequently, the electrical conductivity. Opportunely, the measured Seebeck coefficient varied within a small range upon Sn doping. The excellent performance obtained when Sn2+ ions are prevented from oxidation is rationalized by modeling the system. Calculated band structures disclosed that Sn doping induces convergence of the AgSbSe2 valence bands, accounting for an enhanced electronic effective mass. The dramatically enhanced carrier transport leads to a maximized power factor for AgSb0.98Sn0.02Se2 of 0.63 mW m–1 K–2 at 640 K. Thermally, phonon scattering is significantly enhanced in the NC-based materials, yielding an ultralow thermal conductivity of 0.3 W mK–1 at 666 K. Overall, a record-high figure of merit (zT) is obtained at 666 K for AgSb0.98Sn0.02Se2 at zT = 1.37, well above the values obtained for undoped AgSbSe2, at zT = 0.58 and state-of-art Pb- and Te-free materials, which makes AgSb0.98Sn0.02Se2 an excellent p-type candidate for medium-temperature TE applications.

X-ray Thomson scattering spectra from density functional theory molecular dynamics simulations based on a modified Chihara formula - Schörner, Maximilian; Bethkenhagen, Mandy; Döppner, Tilo; Kraus, Dominik; Fletcher, Luke B.; Glenzer, Siegfried H.; Redmer, Ronald (Physical Review E)
We study ab initio approaches for calculating x-ray Thomson scattering spectra from density functional theory molecular dynamics simulations based on a modified Chihara formula that expresses the inelastic contribution in terms of the dielectric function. We study the electronic dynamic structure factor computed from the Mermin dielectric function using an ab initio electron-ion collision frequency in comparison to computations using a linear-response time-dependent density functional theory (LR-TDDFT) framework for hydrogen and beryllium and investigate the dispersion of free-free and bound-free contributions to the scattering signal. A separate treatment of these contributions, where only the free-free part follows the Mermin dispersion, shows good agreement with LR-TDDFT results for ambient-density beryllium, but breaks down for highly compressed matter where the bound states become pressure ionized. LR-TDDFT is used to reanalyze x-ray Thomson scattering experiments on beryllium demonstrating strong deviations from the plasma conditions inferred with traditional analytic models at small scattering angles.

Finite-range bias in fitting three-body loss to the zero-range model - Agafonova, Sofya; Lemeshko, Mikhail; Volosniev, Artem (Physical Review A)
We study the impact of finite-range physics on the zero-range-model analysis of three-body recombination in ultracold atoms. We find that temperature dependence of the zero-range parameters can vary from one set of measurements to another as it may be driven by the distribution of error bars in the experiment, and not by the underlying three-body physics. To study finite-temperature effects in three-body recombination beyond the zero-range physics, we introduce and examine a finite-range model based upon a hyperspherical formalism. The systematic error discussed in this Letter may provide a significant contribution to the error bars of measured three-body parameters.

An assessment of the ENSO-monsoon teleconnection in a warming climate - Goswami, Bidyut B; An, Soon Il (npj Climate and Atmospheric Science)
The El Niño-Southern Oscillation (ENSO) and the Indian summer monsoon (ISM, or monsoon) are two giants of tropical climate. Here we assess the future evolution of the ENSO-monsoon teleconnection in climate simulations with idealized forcing of CO2 increment at a rate of 1% year-1 starting from a present-day condition (367 p.p.m.) until quadrupling. We find a monotonous weakening of the ENSO-monsoon teleconnection with the increase in CO2. Increased co-occurrences of El Niño and positive Indian Ocean Dipoles (pIODs) in a warmer climate weaken the teleconnection. Co-occurrences of El Niño and pIOD are attributable to mean sea surface temperature (SST) warming that resembles a pIOD-type warming pattern in the Indian Ocean and an El Niño-type warming in the Pacific. Since ENSO is a critical precursor of the strength of the Indian monsoon, a weakening of this relation may mean a less predictable Indian monsoon in a warmer climate.

Selection on the fly: Short-term adaptation to an altered sexual selection regime in Drosophila pseudoobscura - De Castro Barbosa Rodrigues Barata, Carolina; Snook, Rhonda R.; Ritchie, Michael G.; Kosiol, Carolin (Genome biology and evolution)
Experimental evolution studies are powerful approaches to examine the evolutionary history of lab populations. Such studies have shed light on how selection changes phenotypes and genotypes. Most of these studies have not examined the time course of adaptation under sexual selection manipulation, by resequencing the populations’ genomes at multiple time points. Here, we analyze allele frequency trajectories in Drosophila pseudoobscura where we altered their sexual selection regime for 200 generations and sequenced pooled populations at 5 time points. The intensity of sexual selection was either relaxed in monogamous populations (M) or elevated in polyandrous lines (E). We present a comprehensive study of how selection alters population genetics parameters at the chromosome and gene level. We investigate differences in the effective population size—Ne—between the treatments, and perform a genome-wide scan to identify signatures of selection from the time-series data. We found genomic signatures of adaptation to both regimes in D. pseudoobscura. There are more significant variants in E lines as expected from stronger sexual selection. However, we found that the response on the X chromosome was substantial in both treatments, more pronounced in E and restricted to the more recently sex-linked chromosome arm XR in M. In the first generations of experimental evolution, we estimate Ne to be lower on the X in E lines, which might indicate a swift adaptive response at the onset of selection. Additionally, the third chromosome was affected by elevated polyandry whereby its distal end harbors a region showing a strong signal of adaptive evolution especially in E lines.

Asteroseismology with the Roman galactic bulge time-domain survey - Huber, Daniel; Pinsonneault, Marc; Beck, Paul; Bedding, Timothy R.; Joss Bland-Hawthorn, Joss Bland-Hawthorn; Breton, Sylvain N.; Bugnet, Lisa Annabelle; Chaplin, William J.; Garcia, Rafael A.; Grunblatt, Samuel K.; Guzik, Joyce A.; Hekker, Saskia; et al. (arXiv)
Asteroseismology has transformed stellar astrophysics. Red giant asteroseismology is a prime example, with oscillation periods and amplitudes that are readily detectable with time-domain space-based telescopes. These oscillations can be used to infer masses, ages and radii for large numbers of stars, providing unique constraints on stellar populations in our galaxy. The cadence, duration, and spatial resolution of the Roman galactic bulge time-domain survey (GBTDS) are well-suited for asteroseismology and will probe an important population not studied by prior missions. We identify photometric precision as a key requirement for realizing the potential of asteroseismology with Roman. A precision of 1 mmag per 15-min cadence or better for saturated stars will enable detections of the populous red clump star population in the Galactic bulge. If the survey efficiency is better than expected, we argue for repeat observations of the same fields to improve photometric precision, or covering additional fields to expand the stellar population reach if the photometric precision for saturated stars is better than 1 mmag. Asteroseismology is relatively insensitive to the timing of the observations during the mission, and the prime red clump targets can be observed in a single 70 day campaign in any given field. Complementary stellar characterization, particularly astrometry tied to the Gaia system, will also dramatically expand the diagnostic power of asteroseismology. We also highlight synergies to Roman GBTDS exoplanet science using transits and microlensing.

Efficiency and generalization of sparse neural networks - Peste, Elena-Alexandra
Deep learning has become an integral part of a large number of important applications, and many of the recent breakthroughs have been enabled by the ability to train very large models, capable to capture complex patterns and relationships from the data. At the same time, the massive sizes of modern deep learning models have made their deployment to smaller devices more challenging; this is particularly important, as in many applications the users rely on accurate deep learning predictions, but they only have access to devices with limited memory and compute power. One solution to this problem is to prune neural networks, by setting as many of their parameters as possible to zero, to obtain accurate sparse models with lower memory footprint. Despite the great research progress in obtaining sparse models that preserve accuracy, while satisfying memory and computational constraints, there are still many challenges associated with efficiently training sparse models, as well as understanding their generalization properties. The focus of this thesis is to investigate how the training process of sparse models can be made more efficient, and to understand the differences between sparse and dense models in terms of how well they can generalize to changes in the data distribution. We first study a method for co-training sparse and dense models, at a lower cost compared to regular training. With our method we can obtain very accurate sparse networks, and dense models that can recover the baseline accuracy. Furthermore, we are able to more easily analyze the differences, at prediction level, between the sparse-dense model pairs. Next, we investigate the generalization properties of sparse neural networks in more detail, by studying how well different sparse models trained on a larger task can adapt to smaller, more specialized tasks, in a transfer learning scenario. Our analysis across multiple pruning methods and sparsity levels reveals that sparse models provide features that can transfer similarly to or better than the dense baseline. However, the choice of the pruning method plays an important role, and can influence the results when the features are fixed (linear finetuning), or when they are allowed to adapt to the new task (full finetuning). Using sparse models with fixed masks for finetuning on new tasks has an important practical advantage, as it enables training neural networks on smaller devices. However, one drawback of current pruning methods is that the entire training cycle has to be repeated to obtain the initial sparse model, for every sparsity target; in consequence, the entire training process is costly and also multiple models need to be stored. In the last part of the thesis we propose a method that can train accurate dense models that are compressible in a single step, to multiple sparsity levels, without additional finetuning. Our method results in sparse models that can be competitive with existing pruning methods, and which can also successfully generalize to new tasks.

Mechanochemical pattern formation across biological scales - Boocock, Daniel R
Pattern formation is of great importance for its contribution across different biological behaviours. During developmental processes for example, patterns of chemical gradients are established to determine cell fate and complex tissue patterns emerge to define structures such as limbs and vascular networks. Patterns are also seen in collectively migrating groups, for instance traveling waves of density emerging in moving animal flocks as well as collectively migrating cells and tissues. To what extent these biological patterns arise spontaneously through the local interaction of individual constituents or are dictated by higher level instructions is still an open question however there is evidence for the involvement of both types of process. Where patterns arise spontaneously there is a long standing interest in how far the interplay of mechanics, e.g. force generation and deformation, and chemistry, e.g. gene regulation and signaling, contributes to the behaviour. This is because many systems are able to both chemically regulate mechanical force production and chemically sense mechanical deformation, forming mechano-chemical feedback loops which can potentially become unstable towards spatio and/or temporal patterning. We work with experimental collaborators to investigate the possibility that this type of interaction drives pattern formation in biological systems at different scales. We focus first on tissue-level ERK-density waves observed during the wound healing response across different systems where many previous studies have proposed that patterns depend on polarized cell migration and arise from a mechanical flocking-like mechanism. By combining theory with mechanical and optogenetic perturbation experiments on in vitro monolayers we instead find evidence for mechanochemical pattern formation involving only scalar bilateral feedbacks between ERK signaling and cell contraction. We perform further modeling and experiment to study how this instability couples with polar cell migration in order to produce a robust and efficient wound healing response. In a following chapter we implement ERK-density coupling and cell migration in a 2D active vertex model to investigate the interaction of ERK-density patterning with different tissue rheologies and find that the spatio-temporal dynamics are able to both locally and globally fluidize a tissue across the solid-fluid glass transition. In a last chapter we move towards lower spatial scales in the context of subcellular patterning of the cell cytoskeleton where we investigate the transition between phases of spatially homogeneous temporal oscillations and chaotic spatio-temporal patterning in the dynamics of myosin and ROCK activities (a motor component of the actomyosin cytoskeleton and its activator). Experimental evidence supports an intrinsic chemical oscillator which we encode in a reaction model and couple to a contractile active gel description of the cell cortex. The model exhibits phases of chemical oscillations and contractile spatial patterning which reproduce many features of the dynamics seen in Drosophila oocyte epithelia in vivo. However, additional pharmacological perturbations to inhibit myosin contractility leaves the role of contractile instability unclear. We discuss alternative hypotheses and investigate the possibility of reaction-diffusion instability.

Many-body localization proximity effect in a two-species bosonic Hubbard model - Brighi, Pietro; Ljubotina, Marko; Abanin, Dmitry A.; Serbyn, Maksym (Physical Review B)
The many-body localization (MBL) proximity effect is an intriguing phenomenon where a thermal bath localizes due to the interaction with a disordered system. The interplay of thermal and nonergodic behavior in these systems gives rise to a rich phase diagram, whose exploration is an active field of research. In this paper, we study a bosonic Hubbard model featuring two particle species representing the bath and the disordered system. Using state-of-the-art numerical techniques, we investigate the dynamics of the model in different regimes, based on which we obtain a tentative phase diagram as a function of coupling strength and bath size. When the bath is composed of a single particle, we observe clear signatures of a transition from an MBL proximity effect to a delocalized phase. Increasing the bath size, however, its thermalizing effect becomes stronger and eventually the whole system delocalizes in the range of moderate interaction strengths studied. In this regime, we characterize particle transport, revealing diffusive behavior of the originally localized bosons.

Diagrammatic Monte Carlo for electronic correlation in molecules: High-order many-body perturbation theory with low scaling - Bighin, Giacomo; Ho, Quoc P; Lemeshko, Mikhail; Tscherbul, T. V. (Physical Review B)
We present a low-scaling diagrammatic Monte Carlo approach to molecular correlation energies. Using combinatorial graph theory to encode many-body Hugenholtz diagrams, we sample the Møller-Plesset (MPn) perturbation series, obtaining accurate correlation energies up to n=5, with quadratic scaling in the number of basis functions. Our technique reduces the computational complexity of the molecular many-fermion correlation problem, opening up the possibility of low-scaling, accurate stochastic computations for a wide class of many-body systems described by Hugenholtz diagrams.

Visible-light-mediated oxidative debenzylation of 3-O-Benzyl-1,2:5,6-di-O-isopropylidene-α-D-glucofuranose - Madani, Amiera; Sletten, Eric T.; Cavedon, Cristian; Seeberger, Peter H.; Pieber, Bartholomäus (Organic Syntheses)

Dynamic pathogen detection and social feedback shape collective hygiene in ants - Casillas Perez, Barbara E; Bod'Ová, Katarína; Grasse, Anna V; Tkačik, Gašper; Cremer, Sylvia (Nature Communications)
Cooperative disease defense emerges as group-level collective behavior, yet how group members make the underlying individual decisions is poorly understood. Using garden ants and fungal pathogens as an experimental model, we derive the rules governing individual ant grooming choices and show how they produce colony-level hygiene. Time-resolved behavioral analysis, pathogen quantification, and probabilistic modeling reveal that ants increase grooming and preferentially target highly-infectious individuals when perceiving high pathogen load, but transiently suppress grooming after having been groomed by nestmates. Ants thus react to both, the infectivity of others and the social feedback they receive on their own contagiousness. While inferred solely from momentary ant decisions, these behavioral rules quantitatively predict hour-long experimental dynamics, and synergistically combine into efficient colony-wide pathogen removal. Our analyses show that noisy individual decisions based on only local, incomplete, yet dynamically-updated information on pathogen threat and social feedback can lead to potent collective disease defense.

Data from: "Dynamic pathogen detection and social feedback shape collective hygiene in ants" - Cremer, Sylvia
basic data for use in code for experimental data analysis for manuscript under revision: Dynamic pathogen detection and social feedback shape collective hygiene in ants Casillas-Pérez B, Boďová K, Grasse AV, Tkačik G, Cremer S
Keywords: collective behavior; host-pathogen interactions; social immunity; epidemiology; social insects; probabilistic modeling

Curvature-dimension conditions for symmetric quantum Markov semigroups - Wirth, Melchior; Zhang, Haonan (Annales Henri Poincare)
Following up on the recent work on lower Ricci curvature bounds for quantum systems, we introduce two noncommutative versions of curvature-dimension bounds for symmetric quantum Markov semigroups over matrix algebras. Under suitable such curvature-dimension conditions, we prove a family of dimension-dependent functional inequalities, a version of the Bonnet–Myers theorem and concavity of entropy power in the noncommutative setting. We also provide examples satisfying certain curvature-dimension conditions, including Schur multipliers over matrix algebras, Herz–Schur multipliers over group algebras and generalized depolarizing semigroups.

Highly irregular separated nets - Dymond, Michael; Kaluza, Vojtech (Israel Journal of Mathematics)
In 1998 Burago and Kleiner and (independently) McMullen gave examples of separated nets in Euclidean space which are non-bilipschitz equivalent to the integer lattice. We study weaker notions of equivalence of separated nets and demonstrate that such notions also give rise to distinct equivalence classes. Put differently, we find occurrences of particularly strong divergence of separated nets from the integer lattice. Our approach generalises that of Burago and Kleiner and McMullen which takes place largely in a continuous setting. Existence of irregular separated nets is verified via the existence of non-realisable density functions ρ:[0,1]d→(0,∞). In the present work we obtain stronger types of non-realisable densities.
Keywords: Lipschitz; bilipschitz; bounded displacement; modulus of continuity; separated net; non-realisable density; Burago--Kleiner construction

Two-step post-treatment to deliver high performance thermoelectric device with vertical temperature gradient - Zhang, Li; Liu, Xingyu; Wu, Ting; Xu, Shengduo; Suo, Guoquan; Ye, Xiaohui; Hou, Xiaojiang; Yang, Yanling; Liu, Qingfeng; Wang, Hongqiang (Applied Surface Science)
The power factor of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) film can be significantly improved by optimizing the oxidation level of the film in oxidation and reduction processes. However, precise control over the oxidation and reduction effects in PEDOT:PSS remains a challenge, which greatly sacrifices both S and σ. Here, we propose a two-step post-treatment using a mixture of ethylene glycol (EG) and Arginine (Arg) and sulfuric acid (H2SO4) in sequence to engineer high-performance PEDOT:PSS thermoelectric films. The high-polarity EG dopant removes the excess non-ionized PSS and induces benzenoid-to-quinoid conformational change in the PEDOT:PSS films. In particular, basic amino acid Arg tunes the oxidation level of PEDOT:PSS and prevents the films from over-oxidation during H2SO4 post-treatment, leading to increased S. The following H2SO4 post-treatment further induces highly orientated lamellar stacking microstructures to increase σ, yielding a maximum power factor of 170.6 μW m−1 K−2 at 460 K. Moreover, a novel trigonal-shape thermoelectric device is designed and assembled by the as-prepared PEDOT:PSS films in order to harvest heat via a vertical temperature gradient. An output power density of 33 μW cm−2 is generated at a temperature difference of 40 K, showing the potential application for low-grade wearable electronic devices.
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Optimal decay of the parabolic semigroup in stochastic homogenization for correlated coefficient fields - Clozeau, Nicolas (Stochastics and Partial Differential Equations: Analysis and Computations)
We study the large scale behavior of elliptic systems with stationary random coefficient that have only slowly decaying correlations. To this aim we analyze the so-called corrector equation, a degenerate elliptic equation posed in the probability space. In this contribution, we use a parabolic approach and optimally quantify the time decay of the semigroup. For the theoretical point of view, we prove an optimal decay estimate of the gradient and flux of the corrector when spatially averaged over a scale R larger than 1. For the numerical point of view, our results provide convenient tools for the analysis of various numerical methods.

Quenched universality for deformed Wigner matrices - Cipolloni, Giorgio; Erdös, László; Schröder, Dominik J (Probability Theory and Related Fields)
Following E. Wigner’s original vision, we prove that sampling the eigenvalue gaps within the bulk spectrum of a fixed (deformed) Wigner matrix H yields the celebrated Wigner-Dyson-Mehta universal statistics with high probability. Similarly, we prove universality for a monoparametric family of deformed Wigner matrices H+xA with a deterministic Hermitian matrix A and a fixed Wigner matrix H, just using the randomness of a single scalar real random variable x. Both results constitute quenched versions of bulk universality that has so far only been proven in annealed sense with respect to the probability space of the matrix ensemble.

Fine tuning of defects enables high carrier mobility and enhanced thermoelectric performance of n-type PbTe - Wang, Siqi; Chang, Cheng; Bai, Shulin; Qin, Bingchao; Zhu, Yingcai; Zhan, Shaoping; Zheng, Junqing; Tang, Shuwei; Zhao, Li Dong (Chemistry of Materials)
High carrier mobility is critical to improving thermoelectric performance over a broad temperature range. However, traditional doping inevitably deteriorates carrier mobility. Herein, we develop a strategy for fine tuning of defects to improve carrier mobility. To begin, n-type PbTe is created by compensating for the intrinsic Pb vacancy in bare PbTe. Excess Pb2+ reduces vacancy scattering, resulting in a high carrier mobility of ∼3400 cm2 V–1 s–1. Then, excess Ag is introduced to compensate for the remaining intrinsic Pb vacancies. We find that excess Ag exhibits a dynamic doping process with increasing temperatures, increasing both the carrier concentration and carrier mobility throughout a wide temperature range; specifically, an ultrahigh carrier mobility ∼7300 cm2 V–1 s–1 is obtained for Pb1.01Te + 0.002Ag at 300 K. Moreover, the dynamic doping-induced high carrier concentration suppresses the bipolar thermal conductivity at high temperatures. The final step is using iodine to optimize the carrier concentration to ∼1019 cm–3. Ultimately, a maximum ZT value of ∼1.5 and a large average ZTave value of ∼1.0 at 300–773 K are obtained for Pb1.01Te0.998I0.002 + 0.002Ag. These findings demonstrate that fine tuning of defects with <0.5% impurities can remarkably enhance carrier mobility and improve thermoelectric performance.

Inserting one edge into a simple drawing is hard - Arroyo Guevara, Alan M; Klute, Fabian; Parada, Irene; Vogtenhuber, Birgit; Seidel, Raimund; Wiedera, Tilo (Discrete and Computational Geometry)
A simple drawing D(G) of a graph G is one where each pair of edges share at most one point: either a common endpoint or a proper crossing. An edge e in the complement of G can be inserted into D(G) if there exists a simple drawing of G+e extending D(G). As a result of Levi’s Enlargement Lemma, if a drawing is rectilinear (pseudolinear), that is, the edges can be extended into an arrangement of lines (pseudolines), then any edge in the complement of G can be inserted. In contrast, we show that it is NP-complete to decide whether one edge can be inserted into a simple drawing. This remains true even if we assume that the drawing is pseudocircular, that is, the edges can be extended to an arrangement of pseudocircles. On the positive side, we show that, given an arrangement of pseudocircles A and a pseudosegment σ, it can be decided in polynomial time whether there exists a pseudocircle Φσ extending σ for which A∪Φσ is again an arrangement of pseudocircles.

The splay-list: A distribution-adaptive concurrent skip-list - Aksenov, Vitalii; Alistarh, Dan-Adrian; Drozdova, Alexandra; Mohtashami, Amirkeivan (Distributed Computing)
The design and implementation of efficient concurrent data structures has seen significant attention. However, most of this work has focused on concurrent data structures providing good worst-case guarantees, although, in real workloads, objects are often accessed at different rates. Efficient distribution-adaptive data structures, such as splay-trees, are known in the sequential case; however, they often are hard to translate efficiently to the concurrent case. We investigate distribution-adaptive concurrent data structures, and propose a new design called the splay-list. At a high level, the splay-list is similar to a standard skip-list, with the key distinction that the height of each element adapts dynamically to its access rate: popular elements “move up,” whereas rarely-accessed elements decrease in height. We show that the splay-list provides order-optimal amortized complexity bounds for a subset of operations, while being amenable to efficient concurrent implementation. Experiments show that the splay-list can leverage distribution-adaptivity for performance, and can outperform the only previously-known distribution-adaptive concurrent design in certain workloads.

On the origin and structure of haplotype blocks - Shipilina, Daria; Pal, Arka; Stankowski, Sean; Chan, Yingguang Frank; Barton, Nicholas H (Molecular Ecology)
The term “haplotype block” is commonly used in the developing field of haplotype-based inference methods. We argue that the term should be defined based on the structure of the Ancestral Recombination Graph (ARG), which contains complete information on the ancestry of a sample. We use simulated examples to demonstrate key features of the relationship between haplotype blocks and ancestral structure, emphasizing the stochasticity of the processes that generate them. Even the simplest cases of neutrality or of a “hard” selective sweep produce a rich structure, often missed by commonly used statistics. We highlight a number of novel methods for inferring haplotype structure, based on the full ARG, or on a sequence of trees, and illustrate how they can be used to define haplotype blocks using an empirical data set. While the advent of new, computationally efficient methods makes it possible to apply these concepts broadly, they (and additional new methods) could benefit from adding features to explore haplotype blocks, as we define them. Understanding and applying the concept of the haplotype block will be essential to fully exploit long and linked-read sequencing technologies.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics

Aromatic ring flips in differently packed ubiquitin protein crystals from MAS NMR and MD - Gauto, Diego F.; Lebedenko, Olga O.; Becker, Lea Marie; Ayala, Isabel; Lichtenecker, Roman; Skrynnikov, Nikolai R.; Schanda, Paul (Journal of Structural Biology: X)
Probing the dynamics of aromatic side chains provides important insights into the behavior of a protein because flips of aromatic rings in a protein’s hydrophobic core report on breathing motion involving a large part of the protein. Inherently invisible to crystallography, aromatic motions have been primarily studied by solution NMR. The question how packing of proteins in crystals affects ring flips has, thus, remained largely unexplored. Here we apply magic-angle spinning NMR, advanced phenylalanine 1H-13C/2H isotope labeling and MD simulation to a protein in three different crystal packing environments to shed light onto possible impact of packing on ring flips. The flips of the two Phe residues in ubiquitin, both surface exposed, appear remarkably conserved in the different crystal forms, even though the intermolecular packing is quite different: Phe4 flips on a ca. 10–20 ns time scale, and Phe45 are broadened in all crystals, presumably due to µs motion. Our findings suggest that intramolecular influences are more important for ring flips than intermolecular (packing) effects.
Keywords: Structural Biology

In vitro reconstitution of small GTPase regulation - Loose, Martin; Auer, Albert; Brognara, Gabriel; Budiman, Hanifatul R; Kowalski, Lukasz M; Matijevic, Ivana (FEBS Letters)
Small GTPases play essential roles in the organization of eukaryotic cells. In recent years, it has become clear that their intracellular functions result from intricate biochemical networks of the GTPase and their regulators that dynamically bind to a membrane surface. Due to the inherent complexities of their interactions, however, revealing the underlying mechanisms of action is often difficult to achieve from in vivo studies. This review summarizes in vitro reconstitution approaches developed to obtain a better mechanistic understanding of how small GTPase activities are regulated in space and time.
Keywords: Cell Biology; Genetics; Molecular Biology; Biochemistry; Structural Biology; Biophysics

Long-lived counters with polylogarithmic amortized step complexity - Baig, Mirza Ahad; Hendler, Danny; Milani, Alessia; Travers, Corentin (Distributed Computing)
A shared-memory counter is a widely-used and well-studied concurrent object. It supports two operations: An Inc operation that increases its value by 1 and a Read operation that returns its current value. In Jayanti et al (SIAM J Comput, 30(2), 2000), Jayanti, Tan and Toueg proved a linear lower bound on the worst-case step complexity of obstruction-free implementations, from read-write registers, of a large class of shared objects that includes counters. The lower bound leaves open the question of finding counter implementations with sub-linear amortized step complexity. In this work, we address this gap. We show that n-process, wait-free and linearizable counters can be implemented from read-write registers with O(log2n) amortized step complexity. This is the first counter algorithm from read-write registers that provides sub-linear amortized step complexity in executions of arbitrary length. Since a logarithmic lower bound on the amortized step complexity of obstruction-free counter implementations exists, our upper bound is within a logarithmic factor of the optimal. The worst-case step complexity of the construction remains linear, which is optimal. This is obtained thanks to a new max register construction with O(logn) amortized step complexity in executions of arbitrary length in which the value stored in the register does not grow too quickly. We then leverage an existing counter algorithm by Aspnes, Attiya and Censor-Hillel [1] in which we “plug” our max register implementation to show that it remains linearizable while achieving O(log2n) amortized step complexity.
Keywords: Computational Theory and Mathematics; Computer Networks and Communications; Hardware and Architecture; Theoretical Computer Science

Experimental analysis of Cascade CSTRs with step and pulse inputs - Khatoon, Bushra; Kamil, Shoaib; Babu, Hitesh; Siraj Alam, M. (Materials Today: Proceedings)
In industrial reactors and equipment, non-ideality is quite a common phenomenon rather than an exception. These deviations from ideality impact the process's overall efficiency and the effectiveness of the equipment. To recognize the associated non-ideality, one needs to have enough understanding of the formulation of the equations and in-depth knowledge of the residence time distribution (RTD) data of real reactors. In the current work, step input and pulse input were used to create RTD data for Cascade continuous stirred tank reactors (CSTRs). For the aforementioned configuration, experiments were run at various flow rates to validate the developed characteristic equations. To produce RTD data, distilled water was utilized as the flowing fluid, and NaOH was the tracer substance. The ideal behavior of tracer concentration exits age distribution, and cumulative fraction for each setup and each input was plotted and experimental results were compared with perfect behavior. Deviation of concentration exit age distribution and cumulative fractional distribution from ideal behavior is more in pulse input as compared to a step input. For ideal cases, the exit age distribution curve and cumulative fraction curves are independent of the type of input. But a significant difference was observed for the two cases, which may be due to non-measurable fluctuations in volumetric flow rate, non-achievement of instant injection of tracer in case of pulse input, and slight variations in the sampling period. Further, with increasing flow rate, concentration, exit age, and cumulative fractional curves shifted upward, and this behavior matches with the actual case.
Keywords: General Medicine

The olfactory limbus of the red fox (Vulpes vulpes). New insights regarding a noncanonical olfactory bulb pathway - Ortiz-Leal, Irene; Torres, Mateo V.; Vargas Barroso, Victor M; Fidalgo, Luis Eusebio; López-Beceiro, Ana María; Larriva-Sahd, Jorge A.; Sánchez-Quinteiro, Pablo (Frontiers in Neuroanatomy)
Introduction: The olfactory system in most mammals is divided into several subsystems based on the anatomical locations of the neuroreceptor cells involved and the receptor families that are expressed. In addition to the main olfactory system and the vomeronasal system, a range of olfactory subsystems converge onto the transition zone located between the main olfactory bulb (MOB) and the accessory olfactory bulb (AOB), which has been termed the olfactory limbus (OL). The OL contains specialized glomeruli that receive noncanonical sensory afferences and which interact with the MOB and AOB. Little is known regarding the olfactory subsystems of mammals other than laboratory rodents. Methods: We have focused on characterizing the OL in the red fox by performing general and specific histological stainings on serial sections, using both single and double immunohistochemical and lectin-histochemical labeling techniques. Results: As a result, we have been able to determine that the OL of the red fox (Vulpes vulpes) displays an uncommonly high degree of development and complexity. Discussion: This makes this species a novel mammalian model, the study of which could improve our understanding of the noncanonical pathways involved in the processing of chemosensory cues.

The Bose Gas in a box with Neumann boundary conditions - Boccato, Chiara; Seiringer, Robert (Annales Henri Poincare)
We consider a gas of n bosonic particles confined in a box [−ℓ/2,ℓ/2]3 with Neumann boundary conditions. We prove Bose–Einstein condensation in the Gross–Pitaevskii regime, with an optimal bound on the condensate depletion. Moreover, our lower bound for the ground state energy in a small box [−ℓ/2,ℓ/2]3 implies (via Neumann bracketing) a lower bound for the ground state energy of N bosons in a large box [−L/2,L/2]3 with density ρ=N/L3 in the thermodynamic limit.

Computing the volume, surface area, mean, and Gaussian curvatures of molecules and their derivatives - Koehl, Patrice; Akopyan, Arseniy; Edelsbrunner, Herbert (Journal of Chemical Information and Modeling)
Geometry is crucial in our efforts to comprehend the structures and dynamics of biomolecules. For example, volume, surface area, and integrated mean and Gaussian curvature of the union of balls representing a molecule are used to quantify its interactions with the water surrounding it in the morphometric implicit solvent models. The Alpha Shape theory provides an accurate and reliable method for computing these geometric measures. In this paper, we derive homogeneous formulas for the expressions of these measures and their derivatives with respect to the atomic coordinates, and we provide algorithms that implement them into a new software package, AlphaMol. The only variables in these formulas are the interatomic distances, making them insensitive to translations and rotations. AlphaMol includes a sequential algorithm and a parallel algorithm. In the parallel version, we partition the atoms of the molecule of interest into 3D rectangular blocks, using a kd-tree algorithm. We then apply the sequential algorithm of AlphaMol to each block, augmented by a buffer zone to account for atoms whose ball representations may partially cover the block. The current parallel version of AlphaMol leads to a 20-fold speed-up compared to an independent serial implementation when using 32 processors. For instance, it takes 31 s to compute the geometric measures and derivatives of each atom in a viral capsid with more than 26 million atoms on 32 Intel processors running at 2.7 GHz. The presence of the buffer zones, however, leads to redundant computations, which ultimately limit the impact of using multiple processors. AlphaMol is available as an OpenSource software.

Pathogen evasion of social immunity - Stock, Miriam; Milutinovic, Barbara; Hönigsberger, Michaela; Grasse, Anna V; Wiesenhofer, Florian; Kampleitner, Niklas; Narasimhan, Madhumitha; Schmitt, Thomas; Cremer, Sylvia (Nature Ecology and Evolution)
Treating sick group members is a hallmark of collective disease defence in vertebrates and invertebrates alike. Despite substantial effects on pathogen fitness and epidemiology, it is still largely unknown how pathogens react to the selection pressure imposed by care intervention. Using social insects and pathogenic fungi, we here performed a serial passage experiment in the presence or absence of colony members, which provide social immunity by grooming off infectious spores from exposed individuals. We found specific effects on pathogen diversity, virulence and transmission. Under selection of social immunity, pathogens invested into higher spore production, but spores were less virulent. Notably, they also elicited a lower grooming response in colony members, compared with spores from the individual host selection lines. Chemical spore analysis suggested that the spores from social selection lines escaped the caregivers’ detection by containing lower levels of ergosterol, a key fungal membrane component. Experimental application of chemically pure ergosterol indeed induced sanitary grooming, supporting its role as a microbe-associated cue triggering host social immunity against fungal pathogens. By reducing this detection cue, pathogens were able to evade the otherwise very effective collective disease defences of their social hosts.

Slower-X: Reduced efficiency of selection in the early stages of X chromosome evolution - Mrnjavac, Andrea; Khudiakova, Kseniia; Barton, Nicholas H; Vicoso, Beatriz (Evolution Letters)
Differentiated X chromosomes are expected to have higher rates of adaptive divergence than autosomes, if new beneficial mutations are recessive (the “faster-X effect”), largely because these mutations are immediately exposed to selection in males. The evolution of X chromosomes after they stop recombining in males, but before they become hemizygous, has not been well explored theoretically. We use the diffusion approximation to infer substitution rates of beneficial and deleterious mutations under such a scenario. Our results show that selection is less efficient on diploid X loci than on autosomal and hemizygous X loci under a wide range of parameters. This “slower-X” effect is stronger for genes affecting primarily (or only) male fitness, and for sexually antagonistic genes. These unusual dynamics suggest that some of the peculiar features of X chromosomes, such as the differential accumulation of genes with sex-specific functions, may start arising earlier than previously appreciated.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics

Principles of neural stem cell lineage progression: Insights from developing cerebral cortex - Hippenmeyer, Simon (Current Opinion in Neurobiology)
How to generate a brain of correct size and with appropriate cell-type diversity during development is a major question in Neuroscience. In the developing neocortex, radial glial progenitor (RGP) cells are the main neural stem cells that produce cortical excitatory projection neurons, glial cells, and establish the prospective postnatal stem cell niche in the lateral ventricles. RGPs follow a tightly orchestrated developmental program that when disrupted can result in severe cortical malformations such as microcephaly and megalencephaly. The precise cellular and molecular mechanisms instructing faithful RGP lineage progression are however not well understood. This review will summarize recent conceptual advances that contribute to our understanding of the general principles of RGP lineage progression.
Keywords: General Neuroscience

On the trace embedding and its applications to evolution equations - Agresti, Antonio; Lindemulder, Nick; Veraar, Mark (Mathematische Nachrichten)
In this paper, we consider traces at initial times for functions with mixed time-space smoothness. Such results are often needed in the theory of evolution equations. Our result extends and unifies many previous results. Our main improvement is that we can allow general interpolation couples. The abstract results are applied to regularity problems for fractional evolution equations and stochastic evolution equations, where uniform trace estimates on the half-line are shown.

Bogoliubov dynamics and higher-order corrections for the regularized Nelson model - Falconi, Marco; Leopold, Nikolai K; Mitrouskas, David Johannes; Petrat, Sören P (Reviews in Mathematical Physics)
We study the time evolution of the Nelson model in a mean-field limit in which N nonrelativistic bosons weakly couple (with respect to the particle number) to a positive or zero mass quantized scalar field. Our main result is the derivation of the Bogoliubov dynamics and higher-order corrections. More precisely, we prove the convergence of the approximate wave function to the many-body wave function in norm, with a convergence rate proportional to the number of corrections taken into account in the approximation. We prove an analogous result for the unitary propagator. As an application, we derive a simple system of partial differential equations describing the time evolution of the first- and second-order approximations to the one-particle reduced density matrices of the particles and the quantum field, respectively.

Statistical modeling of adaptive neural networks explains co-existence of avalanches and oscillations in resting human brain - Lombardi, Fabrizio; Pepic, Selver; Shriki, Oren; Tkačik, Gašper; De Martino, Daniele (Nature Computational Science)
Neurons in the brain are wired into adaptive networks that exhibit collective dynamics as diverse as scale-specific oscillations and scale-free neuronal avalanches. Although existing models account for oscillations and avalanches separately, they typically do not explain both phenomena, are too complex to analyze analytically or intractable to infer from data rigorously. Here we propose a feedback-driven Ising-like class of neural networks that captures avalanches and oscillations simultaneously and quantitatively. In the simplest yet fully microscopic model version, we can analytically compute the phase diagram and make direct contact with human brain resting-state activity recordings via tractable inference of the model’s two essential parameters. The inferred model quantitatively captures the dynamics over a broad range of scales, from single sensor oscillations to collective behaviors of extreme events and neuronal avalanches. Importantly, the inferred parameters indicate that the co-existence of scale-specific (oscillations) and scale-free (avalanches) dynamics occurs close to a non-equilibrium critical point at the onset of self-sustained oscillations.

Efficient data structures for incremental exact and approximate maximum flow - Goranci, Gramoz; Henzinger, Monika H (50th International Colloquium on Automata, Languages, and Programming)
We show an (1+ϵ)-approximation algorithm for maintaining maximum s-t flow under m edge insertions in m1/2+o(1)ϵ−1/2 amortized update time for directed, unweighted graphs. This constitutes the first sublinear dynamic maximum flow algorithm in general sparse graphs with arbitrarily good approximation guarantee.

Parameter estimation for Gibbs distributions - Harris, David G.; Kolmogorov, Vladimir (50th International Colloquium on Automata, Languages, and Programming)
A central problem in computational statistics is to convert a procedure for sampling combinatorial objects into a procedure for counting those objects, and vice versa. We will consider sampling problems which come from Gibbs distributions, which are families of probability distributions over a discrete space Ω with probability mass function of the form μ^Ω_β(ω) ∝ e^{β H(ω)} for β in an interval [β_min, β_max] and H(ω) ∈ {0} ∪ [1, n]. The partition function is the normalization factor Z(β) = ∑_{ω ∈ Ω} e^{β H(ω)}, and the log partition ratio is defined as q = (log Z(β_max))/Z(β_min) We develop a number of algorithms to estimate the counts c_x using roughly Õ(q/ε²) samples for general Gibbs distributions and Õ(n²/ε²) samples for integer-valued distributions (ignoring some second-order terms and parameters), We show this is optimal up to logarithmic factors. We illustrate with improved algorithms for counting connected subgraphs and perfect matchings in a graph.

Faster submodular maximization for several classes of matroids - Henzinger, Monika H; Liu, Paul; Vondrák, Jan; Zheng, Da Wei (50th International Colloquium on Automata, Languages, and Programming)
The maximization of submodular functions have found widespread application in areas such as machine learning, combinatorial optimization, and economics, where practitioners often wish to enforce various constraints; the matroid constraint has been investigated extensively due to its algorithmic properties and expressive power. Though tight approximation algorithms for general matroid constraints exist in theory, the running times of such algorithms typically scale quadratically, and are not practical for truly large scale settings. Recent progress has focused on fast algorithms for important classes of matroids given in explicit form. Currently, nearly-linear time algorithms only exist for graphic and partition matroids [Alina Ene and Huy L. Nguyen, 2019]. In this work, we develop algorithms for monotone submodular maximization constrained by graphic, transversal matroids, or laminar matroids in time near-linear in the size of their representation. Our algorithms achieve an optimal approximation of 1-1/e-ε and both generalize and accelerate the results of Ene and Nguyen [Alina Ene and Huy L. Nguyen, 2019]. In fact, the running time of our algorithm cannot be improved within the fast continuous greedy framework of Badanidiyuru and Vondrák [Ashwinkumar Badanidiyuru and Jan Vondrák, 2014]. To achieve near-linear running time, we make use of dynamic data structures that maintain bases with approximate maximum cardinality and weight under certain element updates. These data structures need to support a weight decrease operation and a novel Freeze operation that allows the algorithm to freeze elements (i.e. force to be contained) in its basis regardless of future data structure operations. For the laminar matroid, we present a new dynamic data structure using the top tree interface of Alstrup, Holm, de Lichtenberg, and Thorup [Stephen Alstrup et al., 2005] that maintains the maximum weight basis under insertions and deletions of elements in O(log n) time. This data structure needs to support certain subtree query and path update operations that are performed every insertion and deletion that are non-trivial to handle in conjunction. For the transversal matroid the Freeze operation corresponds to requiring the data structure to keep a certain set S of vertices matched, a property that we call S-stability. While there is a large body of work on dynamic matching algorithms, none are S-stable and maintain an approximate maximum weight matching under vertex updates. We give the first such algorithm for bipartite graphs with total running time linear (up to log factors) in the number of edges.

Zero-rate thresholds and new capacity bounds for list-decoding and list-recovery - Resch, Nicolas; Yuan, Chen; Zhang, Yihan (50th International Colloquium on Automata, Languages, and Programming)
In this work we consider the list-decodability and list-recoverability of arbitrary q-ary codes, for all integer values of q ≥ 2. A code is called (p,L)_q-list-decodable if every radius pn Hamming ball contains less than L codewords; (p,𝓁,L)_q-list-recoverability is a generalization where we place radius pn Hamming balls on every point of a combinatorial rectangle with side length 𝓁 and again stipulate that there be less than L codewords. Our main contribution is to precisely calculate the maximum value of p for which there exist infinite families of positive rate (p,𝓁,L)_q-list-recoverable codes, the quantity we call the zero-rate threshold. Denoting this value by p_*, we in fact show that codes correcting a p_*+ε fraction of errors must have size O_ε(1), i.e., independent of n. Such a result is typically referred to as a "Plotkin bound." To complement this, a standard random code with expurgation construction shows that there exist positive rate codes correcting a p_*-ε fraction of errors. We also follow a classical proof template (typically attributed to Elias and Bassalygo) to derive from the zero-rate threshold other tradeoffs between rate and decoding radius for list-decoding and list-recovery. Technically, proving the Plotkin bound boils down to demonstrating the Schur convexity of a certain function defined on the q-simplex as well as the convexity of a univariate function derived from it. We remark that an earlier argument claimed similar results for q-ary list-decoding; however, we point out that this earlier proof is flawed.

Single-collision statistics reveal a global mechanism driven by sample history for contact electrification in granular media - Grosjean, Galien M; Waitukaitis, Scott R (Physical Review Letters)
Models for same-material contact electrification in granular media often rely on a local charge-driving parameter whose spatial variations lead to a stochastic origin for charge exchange. Measuring the charge transfer from individual granular spheres after contacts with substrates of the same material, we find instead a “global” charging behavior, coherent over the sample’s whole surface. Cleaning and baking samples fully resets charging magnitude and direction, which indicates the underlying global parameter is not intrinsic to the material, but acquired from its history. Charging behavior is randomly and irreversibly affected by changes in relative humidity, hinting at a mechanism where adsorbates, in particular, water, are fundamental to the charge-transfer process.
Keywords: General Physics; Electrostatics; Triboelectricity; Soft Matter; Acoustic Levitation; Granular Materials

Cavity quantum electrooptics - Sahu, Rishabh
About a 100 years ago, we discovered that our universe is inherently noisy, that is, measuring any physical quantity with a precision beyond a certain point is not possible because of an omnipresent inherent noise. We call this - the quantum noise. Certain physical processes allow this quantum noise to get correlated in conjugate physical variables. These quantum correlations can be used to go beyond the potential of our inherently noisy universe and obtain a quantum advantage over the classical applications. Quantum noise being inherent also means that, at the fundamental level, the physical quantities are not well defined and therefore, objects can stay in multiple states at the same time. For example, the position of a particle not being well defined means that the particle is in multiple positions at the same time. About 4 decades ago, we started exploring the possibility of using objects which can be in multiple states at the same time to increase the dimensionality in computation. Thus, the field of quantum computing was born. We discovered that using quantum entanglement, a property closely related to quantum correlations, can be used to speed up computation of certain problems, such as factorisation of large numbers, faster than any known classical algorithm. Thus began the pursuit to make quantum computers a reality. Till date, we have explored quantum control over many physical systems including photons, spins, atoms, ions and even simple circuits made up of superconducting material. However, there persists one ubiquitous theme. The more readily a system interacts with an external field or matter, the more easily we can control it. But this also means that such a system can easily interact with a noisy environment and quickly lose its coherence. Consequently, such systems like electron spins need to be protected from the environment to ensure the longevity of their coherence. Other systems like nuclear spins are naturally protected as they do not interact easily with the environment. But, due to the same reason, it is harder to interact with such systems. After decades of experimentation with various systems, we are convinced that no one type of quantum system would be the best for all the quantum applications. We would need hybrid systems which are all interconnected - much like the current internet where all sorts of devices can all talk to each other - but now for quantum devices. A quantum internet. Optical photons are the best contenders to carry information for the quantum internet. They can carry quantum information cheaply and without much loss - the same reasons which has made them the backbone of our current internet. Following this direction, many systems, like trapped ions, have already demonstrated successful quantum links over a large distances using optical photons. However, some of the most promising contenders for quantum computing which are based on microwave frequencies have been left behind. This is because high energy optical photons can adversely affect fragile low-energy microwave systems. In this thesis, we present substantial progress on this missing quantum link between microwave and optics using electrooptical nonlinearities in lithium niobate. The nonlinearities are enhanced by using resonant cavities for all the involved modes leading to observation of strong direct coupling between optical and microwave frequencies. With this strong coupling we are not only able to achieve almost 100% internal conversion efficiency with low added noise, thus presenting a quantum-enabled transducer, but also we are able to observe novel effects such as cooling of a microwave mode using optics. The strong coupling regime also leads to direct observation of dynamical backaction effect between microwave and optical frequencies which are studied in detail here. Finally, we also report first observation of microwave-optics entanglement in form of two-mode squeezed vacuum squeezed 0.7dB below vacuum level. With this new bridge between microwave and optics, the microwave-based quantum technologies can finally be a part of a quantum network which is based on optical photons - putting us one step closer to a future with quantum internet.
Keywords: quantum optics; electrooptics; quantum networks; quantum communication; transduction